Oxygen absorbing laminate for molded components used for blister packaging container

JP2024169653A5Active Publication Date: 2025-04-04DAI NIPPON PRINTING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024165860
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-04-04
Estimated Expiration
2040-07-06

AI Technical Summary

Technical Problem

Existing packaging methods for foods, medical products, and chemicals fail to effectively suppress oxygen-induced deterioration and odor, with current oxygen-absorbing materials having insufficient performance, high cost, and environmental impact.

Method used

A laminate structure comprising a base material layer, an oxygen barrier layer, and an oxygen-absorbing adhesive layer, which includes an oxygen-absorbing compound with unsaturated five-membered rings and an oxidation-promoting catalyst, to create an oxygen-absorbing packaging material for blister containers.

Benefits of technology

The laminate effectively reduces oxygen concentration, minimizes odor, and enhances aroma retention, while reducing packaging costs and waste, and is suitable for flexible packaging applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

PURPOSE: To provide a laminate for molded components of a blister packaging container which has less generated odor and excellent barrier property to oxygen gas, absorbs oxygen in a content storage space to reduce the oxygen concentration and inhibits oxygen-induced deterioration of the content and has excellent balance of heat sealability, low odor property, low oxygen concentration, aroma retention, content resistance and filling and packaging properties, and to provide a packaging material for a molded component, a molded component and a blister packaging container prepared using the laminate for molded components.SOLUTION: There is provided an oxygen absorbing laminate for molded components used for molding components of a blister packaging container, which includes a layer structure obtained by laminating at least a base material layer, an oxygen barrier layer, an oxygen absorbing adhesive layer and a sealant layer in this order, wherein the oxygen absorbing adhesive layer is a layer formed from an oxygen absorbing adhesive composition containing a specific oxygen absorbing compound and an oxygen absorption promoting catalyst.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an oxygen-absorbing laminate for molded parts used in molded parts of blister packaging containers which emits little odor, has barrier properties against oxygen gas from the outside and absorbs oxygen in the content storage space to suppress oxygen-induced deterioration of the contents, and has an excellent balance between aroma retention, content resistance, and heat sealability, and is suitable for filling and packaging, as well as to an oxygen-absorbing packaging material for molded parts, an oxygen-absorbing molded part, and an oxygen-absorbing packaging container made using the molded part, all made from the oxygen-absorbing laminate for molded parts. Note that in the present invention, the term blister packaging container includes PTP packaging containers. [Background technology]

[0002] Conventional packaging methods for preventing the deterioration of contents such as food, medical products, chemical products, and cosmetics due to oxygen have included the use of packaging materials with high oxygen barrier properties, gas replacement of the content storage section with an inert gas such as nitrogen gas, and the inclusion of an oxygen scavenger packaged in reduced iron powder or the like. However, there are problems such as insufficient performance, increased packaging costs, increased garbage as waste, only functioning in moist environments, and the risk of accidental ingestion. Furthermore, Patent Document 1 also describes the development of a packaging material using a resin that has oxygen absorbing properties and emits little odor. However, this resin is polycyclododecene, which is insoluble in polar solvents and has no active hydrogen groups, and is therefore difficult to use as an adhesive raw material for packaging materials made of laminates. Patent Document 2 proposes a laminating adhesive made of a resin using methyltetrahydrophthalic acid as a raw material having oxygen absorbing properties, but this adhesive has the drawback of being unstable due to its low oxygen absorbing properties. Patent Document 3 describes an oxygen-absorbing resin that is a thermoplastic resin having a repeating unit composed of a saturated five-membered ring having a substituent that contains a carbon-carbon double bond and a -CH=CH- group linking the saturated five-membered rings. However, this resin has drawbacks such as being difficult to use due to its poor solubility in solvents and emitting a strong odor. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 5873770 [Patent Document 2] Patent No. 5671816 [Patent Document 3] Patent No. 6505699 Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to provide a laminate for molded parts of a blister packaging container which generates little odor, has excellent barrier properties against oxygen gas, absorbs oxygen in a content storage space to reduce the oxygen concentration and suppresses deterioration of the contents due to oxygen, and has an excellent balance of heat sealability, low odor, low oxygen concentration, aroma retention, content resistance, and filling packaging properties, and to provide a packaging material for molded parts, molded parts, and blister packaging containers produced using the laminate for molded parts. [Means for solving the problem]

[0005] Therefore, in order to solve the above problem, the inventors discovered that a laminate including a layer structure in which at least a base layer, an oxygen barrier layer, an oxygen-absorbing adhesive layer formed from a specific oxygen-absorbing adhesive composition, and a sealant layer are laminated in this order can solve the above problem. That is, the present invention is characterized in the following points. 1. An oxygen-absorbing laminate for molded parts, which is used for molded parts of blister packaging containers, and which includes a layer structure in which at least a base layer, an oxygen barrier layer, an oxygen-absorbing adhesive layer, and a sealant layer are laminated in this order, The oxygen-absorbing adhesive layer is a layer formed from an oxygen-absorbing adhesive composition, The oxygen-absorbing adhesive composition contains at least an oxygen-absorbing compound and an oxidation-promoting catalyst, The oxygen absorbing compound has one or more unsaturated five-membered rings, any bond between the five carbon atoms constituting the unsaturated five-membered ring is a carbon-carbon double bond; A monovalent and / or divalent or higher electron-donating organic group 1 is bonded to the unsaturated five-membered ring; When the number of the unsaturated five-membered ring is one, the five-membered ring or the organic group 1 has a functional group having an active hydrogen or a group in which the active hydrogen of the functional group having an active hydrogen is substituted with a monovalent organic group 2, When the number of the unsaturated five-membered rings is two or more, the unsaturated five-membered rings are bonded to each other via a divalent or higher organic group 2 which substitutes an active hydrogen of an active hydrogen group on each of the five-membered rings or the organic group 1. Oxygen absorbing laminate for molded parts. 2. The structure of the unsaturated five-membered ring, or the structure consisting of the unsaturated five-membered ring and organic group 1, is derived from one or more members selected from the group consisting of cyclopentadiene, dicyclopentadiene, norbornene, and derivatives thereof. 2. The oxygen-absorbing laminate for molded parts according to 1 above. 3. The organic group 2 includes a structural portion derived from an isocyanate compound, or an isocyanate compound and a hydroxyl group-containing compound. 3. The oxygen-absorbing laminate for molded parts according to 1 or 2 above. 4. The isocyanate compound is one or more selected from the group consisting of xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, and derivatives thereof; 4. The oxygen-absorbing laminate for molded parts according to 3 above. 5. The hydroxyl group-containing compound is one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof. 5. The oxygen-absorbing laminate for molded parts according to 3 or 4 above. 6. The organic group 2 does not have a crosslinkable functional group. 6. The oxygen-absorbing laminate for molded parts according to any one of 1 to 5 above. 7. The organic group 2 has one or more crosslinkable functional groups, the crosslinkable functional group is a hydroxyl group and / or an isocyanate group; 6. The oxygen-absorbing laminate for molded parts according to any one of 1 to 5 above. 8. The oxygen-absorbing compound contains one or more compounds selected from the group consisting of compounds represented by the following formulas (1) to (4): 6. The oxygen-absorbing laminate for molded parts according to any one of 1 to 5 above. [ka] [ka] [ka] [ka] (In the formula, a to e are each a number of 1 or more, and R 1 , R 2 , R 3 Each of the is an organic group having one or more carbon atoms, contains at least an alkylene and / or phenylene structure, and further contains a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof. 9. The oxygen-absorbing compound contains a compound represented by the following formula (5): 6. The oxygen-absorbing laminate for molded parts according to any one of 1 to 5 above. [ka] (In the formula, f is a number equal to or greater than 0, and R 4 and R 5Each of the above is an organic group having one or more carbon atoms, containing at least an alkylene and / or phenylene structure, and further may contain a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof. 10. The oxidation-promoting catalyst is a peroxide or a compound containing a cation consisting of a transition metal; 10. The oxygen-absorbing laminate for molded parts according to any one of 1 to 9 above. 11. The compound containing a cation made of a transition metal is a metal soap made of a transition metal compound capable of releasing a cation or complex made of a transition metal and an anion or ligand made of a fatty acid. 11. The oxygen-absorbing laminate for molded parts according to any one of 1 to 10 above. 12. The oxygen absorbing adhesive composition further contains a modifier, The modifying agent contains an isocyanate compound and / or a hydroxyl group-containing compound. 12. The oxygen-absorbing laminate for molded parts according to any one of 1 to 11 above. 13. The isocyanate compound is one or more selected from the group consisting of xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, and derivatives thereof. 13. The oxygen-absorbing laminate for molded parts according to 12 above. 14. The hydroxyl group-containing compound includes one or more selected from the group consisting of polyester polyols, poly(meth)acrylic acid ester polyols, polyalkylene ether diols, and urethane chain-extended polyols thereof. 14. The oxygen-absorbing laminate for molded parts according to 12 or 13 above. 15. An oxygen-absorbing packaging material for molded parts of blister packaging containers, produced using the oxygen-absorbing laminate for molded parts according to any one of 1 to 14 above. 16. An oxygen-absorbing molded part for a blister packaging container, produced using the oxygen-absorbing packaging material for molded parts for a blister packaging container described in 15 above. 17. An oxygen-absorbing blister packaging container produced using the oxygen-absorbing molded part of the blister packaging container described in 16 above, The oxygen barrier layer is a layer located outside the oxygen absorbing adhesive layer. Oxygen absorbing blister packaging container. Effect of the Invention

[0006] According to the present invention, it is possible to obtain a laminate for molded parts of a blister packaging container which generates little odor, has excellent barrier properties against oxygen gas, absorbs oxygen in the content storage space to reduce the oxygen concentration and suppresses deterioration of the contents due to oxygen, and has an excellent balance of heat sealing properties, low odor properties, low oxygen concentration properties, aroma retention properties, content resistance, and filling and packaging properties, as well as a packaging material for molded parts, molded parts, and blister packaging containers produced using the laminate for molded parts. Furthermore, packaging materials made from the laminate of the present invention are particularly suitable for flexible packaging applications, shortening the packaging process, reducing costs, and making the package lighter. Since the package does not require the inclusion of an oxygen absorber as was previously included, this eliminates the risk of the oxygen absorber being accidentally ingested and reduces the amount of waste consisting of the oxygen absorber. [Brief description of the drawings]

[0007] [Figure 1] FIG. 1 is a cross-sectional view showing an example of the layer structure of an oxygen-absorbing laminate for molded parts of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing another example of the layer structure of the oxygen-absorbing laminate for molded parts of the present invention. [Diagram 3] FIG. 1 is a cross-sectional view showing an example of an oxygen-absorbing blister packaging container using the oxygen-absorbing packaging material for molded parts of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The present invention will be described in more detail below. The following description of the constituent elements is an example of an embodiment of the present invention, and the present invention is not limited to these contents as long as it does not exceed the gist of the present invention. In the present invention, the terms film and sheet have the same meaning.

[0009] <Oxygen-absorbing laminate for molded parts> The oxygen-absorbing laminate for molded parts of the present invention is a laminate used for molded parts of blister packaging containers, and includes a layer structure in which at least a base layer, an oxygen barrier layer, an oxygen-absorbing adhesive layer, and a sealant layer are laminated in this order. The oxygen-absorbing laminate for molded parts (hereinafter, also referred to as the oxygen-absorbing laminate) is used to produce an oxygen-absorbing packaging material for molded parts (hereinafter, also referred to as the oxygen-absorbing packaging material) for blister packaging containers. When the oxygen-absorbing blister packaging container (hereinafter also referred to as a blister packaging container or a packaging container) is prepared and heat-sealed with a lid part to form an oxygen-absorbing blister packaging container, the sealant layer is heat-sealed and the oxygen barrier layer is positioned outside the oxygen-absorbing blister packaging container relative to the oxygen-absorbing adhesive layer. By positioning the oxygen barrier layer outside the oxygen-absorbing adhesive layer, the amount of oxygen passing through the molded part from the outside can be reduced, and the efficiency with which the oxygen-absorbing adhesive layer absorbs oxygen in the content storage space and reduces the oxygen concentration can be increased.

[0010] The oxygen absorbing laminate for a molded part may optionally contain layers having various other functions. For example, it may have a base material layer or a printed layer, and may include a reinforcing layer to satisfy various conditions such as deformation resistance, drop impact resistance, pinhole resistance, heat resistance, sealability, quality maintenance, workability, hygiene, and the like. In addition, the packaging material may have a functional layer for improving the oxygen gas barrier property, imparting barrier properties against water vapor and the like, imparting aroma retention to the contents to be filled and packaged, and preventing the contents from having an unpleasant taste or odor. Furthermore, a general-purpose adhesive layer may be included between or within each of the above layers to improve interlayer adhesion.

[0011] [Contents] In the above, examples of the contents include medicines, medical instruments including pre-field syringes, health foods such as vitamins, ham, bacon, cheese, raw meat, metal parts such as screws, and others.

[0012] <Each layer constituting the oxygen absorbing laminate for molded parts> <Oxygen barrier layer> The oxygen barrier layer is a layer in an oxygen-absorbing blister packaging container made from an oxygen-absorbing molded part and a lid part that suppresses oxygen transmission through the molded parts from the outside of the oxygen-absorbing blister packaging container to the internal content storage section. In an oxygen-absorbing blister packaging container, the oxygen barrier layer is positioned outside the oxygen-absorbing adhesive layer, thereby suppressing the transmission of oxygen from outside the oxygen-absorbing blister packaging container, thereby enhancing the effect of the oxygen-absorbing adhesive layer absorbing oxygen in the content storage section of the oxygen-absorbing blister packaging container and reducing the oxygen concentration. The oxygen barrier layer can be made of various oxygen barrier materials. In addition, the oxygen barrier layer may be made of oxygen barrier materials that have gas barrier properties against water vapor, light blocking properties against sunlight, aroma retention properties for the contents, etc., in addition to oxygen. In addition, barrier materials that have gas barrier properties against water vapor, light blocking properties against sunlight, aroma retention properties for the contents, etc., may be used in combination.

[0013] Specifically, the oxygen barrier material may be one or more selected from the group consisting of metal foil, resin film with an inorganic vapor deposition layer, and resin coating film or film made of an oxygen barrier resin. Examples of inorganic compounds in the inorganic vapor deposition layer include metals, metal oxides, metal nitrides, and metal carbides. Among the above, resin films with a metal vapor deposition layer, resin films with a metal oxide vapor deposition layer, and resin coating films or resin films made of barrier resins are particularly preferred, as they have excellent barrier properties against oxygen gas, water vapor, light blocking, aroma retention, etc., and are environmentally friendly in terms of disposal of the container.

[0014] A specific example of the metal foil is aluminum foil, the thickness of which is preferably 6 μm to 40 μm. Specific examples of metal elements constituting the above inorganic compounds include aluminum (Al), silicon (Si), magnesium (Mg), calcium (Ca), potassium (K), tin (Sn), sodium (Na), boron (B), titanium (Ti), lead (Pb), zirconium (Zr), yttrium (Y), zinc (Zn), vanadium (V), barium (Ba), and chromium (Cr).

[0015] Specific examples of inorganic compounds include metals, metal oxides, metal nitrides, and metal carbides made of the above-mentioned metal elements. In addition, indium tin oxide (ITO), SiO X C Y Also included are composite inorganic compounds such as membranes. Specific examples of the inorganic compound of the inorganic vapor deposition layer include silicon nitride, silicon carbide, etc. Among these, silica and alumina are preferable.

[0016] The average composition of an inorganic compound is expressed as, for example, SiO x , AlO x , SiO x C y MO x , M.O. x C y (In the formula, M represents a metal element, and the values ​​of x and y depend on the metal element. The range of X is different for each.) In the case of metal oxides, the value of X can range from 0 to 2 for silicon, 0 to 1.5 for aluminum, 0 to 1 for magnesium, 0 to 1 for calcium, 0 to 0.5 for potassium, 0 to 2 for tin, 0 to 0.5 for sodium, 0 to 1.5 for boron, 0 to 2 for titanium, 0 to 1 for lead, 0 to 2 for zirconium, and 0 to 1.5 for yttrium. The above MO X In the case of x=0, it is metallic and not transparent, and in the range of x, The upper limit is the value when completely oxidized. In the present invention, silicon oxide and aluminum oxide are preferably used, and silicon oxide having an x ​​value in the range of 1.0 to 2.0 and aluminum oxide having an x ​​value in the range of 0.5 to 1.5 can be used. The oxygen barrier layer may be formed of one of these barrier materials, or may be a combination of two or more of them, or may be a mixture of two or more of them. It may be composed of one layer or multiple layers of the same or different compositions, and in the case of multiple layers, they do not have to be laminated adjacently.

[0017] As the resin film supporting the inorganic vapor deposition layer, a resin film that has excellent mechanical, physical, chemical and other properties, and is particularly strong and tough, and has heat resistance, can be used since the inorganic vapor deposition layer is provided on it.

[0018] Specifically, in the present invention, examples of the resin film supporting the inorganic vapor deposition layer include polyester-based resin films such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT), polyamide-based resin films such as various nylons, polyethylene-based resins, polypropylene-based resins, cyclic polyolefin resins, polystyrene-based resins, acrylonitrile-styrene copolymers (AS resins), acrylonitrile-butadiene-styrene copolymers (ABS resins), polyolefin films such as polybutene resin films, polyvinyl chloride-based resins, polycarbonate-based resins, polyimide-based resins, polyamideimide-based resins, polyarylphthalate resins, silicone-based resins, polysulfone-based resins, polyphenylene sulfide-based resins, polyethersulfone-based resins, polyurethane-based resins, cellulose-based resins, poly(meth)acrylic resins, polyvinylidene chloride films, acetal-based resin films, fluorine-based resins, and others. In the present invention, it is preferable to use a resin film made of biaxially oriented polyethylene terephthalate, polyacrylonitrile, ethylene-vinyl alcohol copolymer, non-oriented polypropylene (CPP), low-density polyethylene, linear low-density polyethylene, or the like, which can be heat-sealed or bonded with an adhesive. The resin film used in the vapor-deposited resin film may be a resin film constituting a base layer.

[0019] As a method for forming an inorganic vapor deposition layer, the inorganic vapor deposition layer can be formed on a resin film using, for example, a physical vapor deposition method (Physical Vapor Deposition method, PVD method) such as a vacuum deposition method, a sputtering method, an ion plating method, a cluster ion beam method, or a chemical vapor deposition method (Chemical Vapor Deposition method, CVD method) such as a plasma chemical vapor deposition method, a thermal chemical vapor deposition method, a photochemical vapor deposition method, or the like, using the inorganic compounds as raw materials.

[0020] More specifically, in the above-mentioned PVD method, for example, a take-up type deposition machine is used, and a resin film coming off a winding roll in a vacuum chamber is placed into a deposition chamber, where a deposition source heated in a crucible is evaporated, and if necessary, an inorganic deposition layer is formed on the resin film on a cooled coating drum through a mask while oxygen or the like is sprayed from an oxygen outlet, and then the resin film with the inorganic deposition layer formed thereon is wound up onto a take-up roll, thereby producing a resin film with an inorganic deposition layer according to the present invention.

[0021] Meanwhile, in the above-mentioned CVD method, a mixed gas of, for example, an organic silicon compound as a monomer gas, oxygen gas, an inert gas, etc., supplied from a vapor deposition raw material volatilization and supply device in the vapor deposition chamber, is introduced onto the surface of a resin film unwound from a winding roll arranged in a vapor deposition chamber, on the peripheral surface of a cooling electrode drum, and a resin film on which a vapor deposition layer of silicon oxide is formed by plasma can be produced.

[0022] In the above, the thickness of the inorganic vapor deposition layer is preferably 30 Å to 3000 Å, more preferably 40 Å to 2500 Å, and even more preferably 50 Å to 2000 Å, in order to obtain sufficient oxygen barrier properties. More specifically, in the above PVD method, the thickness of the inorganic vapor deposition layer made of aluminum oxide is preferably 30 Å to 1000 Å, and more preferably about 50 Å to 500 Å. In the above CVD method, the thickness of the inorganic vapor deposition layer made of silicon oxide is preferably 30 Å to 3000 Å, and more preferably 100 Å to 300 Å. In the above, in the case of an inorganic vapor deposition layer made of a metal oxide or an inorganic substance, if the thickness of the inorganic vapor deposition layer exceeds the above range, cracks or the like are likely to occur in the inorganic vapor deposition layer, and there is a risk that the barrier properties will be reduced due to warping, and there are problems such as high material costs, which are undesirable. Also, if the thickness is less than the above range, it is undesirable because it is likely to be difficult to achieve oxygen barrier properties.

[0023] An oxygen barrier resin coating film or an oxygen barrier resin film made of an oxygen barrier resin can also be used as an oxygen barrier material, and can simultaneously exhibit gas barrier properties against water vapor and the like, aroma retention, and the like. Examples of oxygen barrier resins that can be used include films or coatings of resins with excellent gas barrier properties, such as polyvinylidene chloride resins (PVDC), polyester resins, polyamide resins (particularly aromatic polyamides such as nylon MXD6), ethylene-vinyl alcohol copolymers (EVOH) with an ethylene content of 25 mol % to 50 mol % obtained by fully saponifying an ethylene-vinyl acetate copolymer (vinyl acetate is approximately 79 wt % to 92 wt %), polyvinyl alcohol, polyacrylonitrile, and others. The thickness of the oxygen barrier resin coating film or the oxygen barrier resin film is not limited, but is preferably 0.5 μm to 300 μm, and more preferably 1 μm to 100 μm.

[0024] The resin film with an inorganic deposition layer preferably has a water vapor permeability of 3.0 g / m2 or less, as measured in accordance with JIS K7129 at a temperature of 40° C. and a humidity of 100% RH. 2 · day or less, and more preferably 2.0 g / m 2 days or less, and more preferably is 1.5g / m 2 If the water vapor transmission rate is within the above range, the package This makes it possible to sufficiently prevent water vapor from entering the content storage section inside the package from the outside. The resin film with an inorganic vapor deposition layer preferably has an acid permeability of 3.0 cc / m2 or less as measured in accordance with JIS K7126 under an environment of 23°C temperature and 90% RH. 2 a tm·day or less, and more preferably 1.0cc / m 2 ·atm·day or less , and more preferably 0.5 cc / m 2 ·atm·day or less. The oxygen permeability is the above number. If the value range is satisfied, the intrusion of oxygen from the outside of the package into the content-accommodating portion inside the package can be sufficiently suppressed.

[0025] When forming the inorganic deposition layer, SiO x Pretreatment such as plasma reduces the resin to be vapor-deposited. By cleaning the surface of the film and generating polar groups or free radicals on the surface, it is possible to increase the tight adhesion between the inorganic vapor deposition layer and the resin film. Furthermore, when two or more inorganic vapor deposition layers are continuously laminated using a plasma enhanced chemical vapor deposition apparatus consisting of at least two deposition chambers, each layer can be deposited so as to have high gas barrier properties, thereby obtaining gas barrier properties that are even higher than those of a single layer. Furthermore, by continuously depositing the layers without exposing them to the atmosphere, it is possible to prevent foreign matter, dust, etc., which may cause cracks, from being mixed between the inorganic vapor deposition layers, and the gas barrier properties are improved. Furthermore, if the compositions of the vapor-deposited layers are different, the inorganic vapor-deposited layers are different discontinuous layers, so that the permeation of oxygen gas, water vapor, etc. can be more efficiently suppressed.

[0026] When the oxygen barrier layer is formed of a resin film with an inorganic vapor deposition layer, the layer can be laminated by bonding the inorganic vapor deposition layer surface to the base layer via a general-purpose adhesive layer. When laminating a resin film with an inorganic vapor deposition layer, if necessary, in order to strengthen the adhesive strength with other layers, the surface of the resin film with an inorganic vapor deposition layer may be subjected in advance to a physical surface treatment such as corona discharge treatment, ozone treatment, plasma treatment, glow discharge treatment, sandblasting treatment, etc., or a chemical surface treatment such as oxidation treatment using chemicals, to form a surface treatment layer.

[0027] <Oxygen-absorbing adhesive layer> The oxygen-absorbing adhesive layer is a layer formed using an oxygen-absorbing adhesive composition.

[0028] Oxygen-absorbing adhesive composition The oxygen-absorbing adhesive composition of the present invention is an oxygen-absorbing adhesive composition that contains at least an oxygen-absorbing compound and an oxidation-promoting catalyst. The oxygen-absorbing adhesive composition may further contain a modifier, a diluting solvent, various additives, and the like, as necessary.

[0029] The oxygen-absorbing adhesive composition may be prepared by adding an oxygen-absorbing compound to an existing adhesive composition, or the oxygen-absorbing adhesive composition may be prepared using an oxygen-absorbing compound as a resin component. Here, the existing oxygen-absorbing adhesive composition may be a one-liquid oxygen-absorbing adhesive composition or a two-liquid oxygen-absorbing adhesive composition. The oxygen absorbing adhesive composition can contain one or more oxygen absorbing compounds. The oxygen-absorbing adhesive composition and / or the above-mentioned existing adhesive composition may be curable or non-curable. If it is curable, it may be any of heat curable, photocurable, electron beam curable, etc. The oxygen absorbing compound may or may not react with components contained in existing adhesive compositions, or may react with other oxygen absorbing compounds. Depending on the presence or absence of the above reaction and the type of reaction, one or more oxygen absorbing compounds can be selected and used from among those having no functional group, those having a (co)polymerizable functional group, and those having a functional group capable of reacting as a base agent or a curing agent.

[0030] Specifically, for example, an oxygen absorbing compound without a functional group and / or an oxygen absorbing compound with a functional group can be added to a two-liquid urethane adhesive composition containing an isocyanate compound and a hydroxyl group-containing compound. In this case, the functional group is preferably an isocyanate group and / or a hydroxyl group. For example, the oxygen-absorbing adhesive composition can be prepared by combining the main component and curing agent with an isocyanate compound and an oxygen-absorbing compound having a hydroxyl group, with a hydroxyl group-containing compound and an oxygen-absorbing compound having an isocyanate group, or with an oxygen-absorbing compound having a hydroxyl group and an oxygen-absorbing compound having an isocyanate group. The oxygen absorbing adhesive composition is preferably a urethane-based oxygen absorbing adhesive composition.

[0031] The solid content in the oxygen-absorbing adhesive composition is not particularly limited, but is preferably 20% by mass or more and 100% by mass or less.

[0032] The content of the oxygen absorbing compound in the solid content excluding the oxidation-promoting catalyst in the oxygen absorbing adhesive composition is preferably 40% by mass or more and 100% by mass or less. If it is less than the above range, there is a risk that the oxygen absorption will be insufficient. When it is 100% by mass, it means that the oxygen absorbing compound can be used as a resin component of the adhesive composition, and it has sufficient adhesiveness by itself, has a functional group that can be cured by itself, or is used by mixing an oxygen absorbing compound having a functional group as a main agent and an oxygen absorbing compound having a functional group as a curing agent.

[0033] The content of the oxidation-promoting catalyst in the oxygen-absorbing adhesive composition is preferably 10 ppm or more and 6000 ppm or less relative to the oxygen-absorbing compound. If the content is less than the above range, the oxygen absorption may be insufficient, and if the content is more than the above range, the oxygen absorption is likely to become unstable, and the oxygen absorption may be consumed before the package is produced, which may impair the effect of inhibiting deterioration of the package contents due to oxygen after the package is produced.

[0034] [Oxygen absorbing compound] The oxygen absorbing compound of the present invention has oxygen absorbing properties, generates little odor, and can be used alone or as a mixture with a resin or a resin composition. The oxygen-absorbing compound of the present invention is an unsaturated five-membered ring-containing compound having one or more unsaturated five-membered rings, in which any bond between five carbon atoms constituting the unsaturated five-membered ring is a carbon-carbon double bond, and a monovalent and / or divalent or higher electron-donating organic group 1 is bonded to the unsaturated five-membered ring. When there is one unsaturated five-membered ring, the five-membered ring or the organic group 1 has a functional group having active hydrogen, or a group in which the active hydrogen of the functional group having active hydrogen is substituted with a monovalent organic group 2, and when there are two or more unsaturated five-membered rings, the unsaturated five-membered rings are bonded to each other via a divalent or higher organic group 2 that substitutes the active hydrogen of the active hydrogen group on each of the organic groups 1. When there are two or more such unsaturated five-membered rings in one molecule, the unsaturated five-membered rings are bonded to each other via a structure in which an active hydrogen of a functional group having an active hydrogen on each of the five-membered rings or organic group 1 is substituted with a divalent or higher organic group 2. The unsaturated five-membered ring, organic group 1, and organic group 2 present in one molecule may each be one or more kinds, and the number of them may be one or more. The number of organic groups 1 bonded to one unsaturated five-membered ring may be one or more. Furthermore, oxygen The absorbing compound may be a mixture of molecules having two or more structures in which the types and numbers of the unsaturated five-membered rings, organic group 1, and organic group 2 present in one molecule are different, as described above.

[0035] Organic group 1 donates electrons to the unsaturated five-membered ring, thereby increasing the electron density of the carbon-carbon double bond portion of the unsaturated five-membered ring, thereby increasing the reactivity with oxygen and improving the oxygen absorbency. It is preferable that no electron-withdrawing group is bonded to the unsaturated five-membered ring, since the electron-withdrawing group is bonded to the unsaturated five-membered ring, the electron density of the carbon-carbon double bond portion of the unsaturated five-membered ring is lowered, the reactivity with oxygen is reduced, and the oxygen absorption is reduced. Specific molecular structures of the oxygen-absorbing compound include, for example, one unsaturated five-membered ring bonded to a monovalent or divalent organic group 1, one unsaturated five-membered ring bonded to a monovalent or divalent organic group 1 and a monovalent organic group 2 in that order, two unsaturated five-membered rings bonded via a divalent organic group 1 and a divalent organic group 2, and three unsaturated five-membered rings bonded via a divalent organic group 1 and a trivalent organic group 2.

[0036] In addition, the oxygen absorbing compound does not have to have a crosslinkable functional group, but can have one. The crosslinkable functional group may be a functional group that was possessed by the compound from which the organic group 2 is derived, or may be a functional group that has been added by chemical modification. Because the oxygen-absorbing compound has a crosslinkable functional group, when the oxygen-absorbing compound is mixed with a resin or a resin composition, the oxygen-absorbing compound has increased compatibility with the resin or the resin composition or becomes part of the crosslinked structure of the resin or the resin composition, making it less likely to bleed from the resin or the resin composition, or from the cured product of the resin composition, and the content of the oxygen-absorbing compound in the resin or the resin composition can be increased. Specific examples of the crosslinkable functional group include an aliphatic hydroxyl group, an aromatic hydroxyl group, an isocyanate group, an amino group, an epoxy group, a (meth)acrylic group, etc. Among these, an isocyanate group and an aliphatic hydroxyl group are preferred. When the oxygen-absorbing compound has a crosslinkable functional group, the number of the crosslinkable functional group in one molecule is preferably 1 or 2 or more. In addition, the crosslinkable functional group contained in one molecule may be one type or two or more types. The functional group equivalent of the crosslinkable functional group is not particularly limited, but is preferably 500 to 20,000, more preferably 1,000 to 15,000, and even more preferably 1,500 to 10,000.

[0037] The number average molecular weight of the oxygen absorbing compound is preferably 100 to 10,000, more preferably 200 to 5,000, and even more preferably 300 to 2,500. If the number average molecular weight is smaller than the above range, it is likely to precipitate when mixed with a resin or a resin composition. If the number average molecular weight is larger than the above range, it is likely to require a large amount of dilution solvent to be contained when mixed with a resin or a resin composition because the viscosity of the mixture increases, making it difficult to obtain a thick film or layer, and coating suitability is likely to deteriorate.

[0038] The oxygen absorbing action of the oxygen absorbing compound of the present invention can be promoted by heating or adding a catalyst.

[0039] (unsaturated five-membered ring) The unsaturated five-membered ring of the oxygen-absorbing compound has a carbon-carbon double bond therein. Here, the carbon-carbon double bond is any bond between the five carbon atoms constituting the unsaturated five-membered ring, and there may be one or two carbon-carbon double bonds in one unsaturated five-membered ring. The carbon-carbon double bond reacts with oxygen molecules in the air and captures the oxygen molecules, thereby causing the oxygen absorbing compound to exhibit its oxygen absorbing properties. The above-mentioned unsaturated five-membered ring or the unsaturated five-membered ring to which the electron-donating organic group 1 is bonded Examples of compounds from which the oxygen absorbing compound is derived include cyclopentadiene, dicyclopentadiene, norbornene, and derivatives thereof. The oxygen absorbing compound may have an unsaturated five-membered ring derived from one or more of these compounds. The concentration of the unsaturated five-membered ring in the oxygen-absorbing compound is not particularly limited, but is preferably 1% by mass or more and 70% by mass or less, and more preferably 5% by mass or more and 60% by mass or less. If the concentration is lower than the above range, the oxygen absorption is likely to be insufficient, and it is difficult to obtain an oxygen-absorbing compound with a higher absorption capacity than the above range, and the balance between various physical properties is likely to be poor.

[0040] (Electron-donating organic group 1) Specific examples of the organic group 1 include an alkyl group, an alkylene group, a cyclic alkylene group, etc. Among these, a cyclic alkylene group is preferable, and one which constitutes an aliphatic bicyclic alkylene group together with the unsaturated five-membered ring is more preferable. Specific examples of the cyclic alkylene group include a cyclopropylene group, a cyclobutylene group, a cyclopentylene group, a cyclohexylene group, a cycloheptylene group, a cyclooctylene group, etc. Among these, a cyclopentylene group is more preferable.

[0041] (Electron-withdrawing organic group) Specific examples of the electron-withdrawing group include a phenyl group, a phenylene group, a carbonyl group, and a halogen. Indenes and coumarones in which only these electron-withdrawing groups are bonded to an unsaturated five-membered ring have a low electron density in the carbon-carbon double bond portion of the unsaturated five-membered ring, which reduces the reactivity with oxygen and results in low oxygen absorption.

[0042] (Functional group having active hydrogen) A functional group having an active hydrogen is chemically reactive. Specific examples of the functional group having an active hydrogen include a primary amino group, a secondary amino group, an aliphatic hydroxyl group, an aromatic hydroxyl group, an imino group, a carboxyl group, a urethane group, and a urea group. Among these, a primary amino group, a secondary amino group, an aliphatic hydroxyl group, and an aromatic hydroxyl group are preferred, and an aliphatic hydroxyl group is more preferred.

[0043] (organic group 2) Organic group 2 is a monovalent and / or divalent or higher group that substitutes an active hydrogen of a functional group having an active hydrogen on the five-membered ring or organic group 1 and is bonded to the five-membered ring or organic group 1. When there are two or more such unsaturated five-membered rings in one molecule, the unsaturated five-membered rings are bonded to each other via a structure in which the active hydrogen of a functional group having an active hydrogen is substituted with a divalent or higher organic group 2. As a specific example, a functional group having an active hydrogen on organic group 1 reacts with an isocyanate group of an isocyanate compound having a structural portion from which organic group 2 is derived, and the active hydrogen is substituted for organic group 2, resulting in bonding via a urethane group. By bonding the organic group 2, the oxygen absorbing compound can have two or more of the unsaturated five-membered rings in one molecule, and furthermore, when mixed with a resin or a resin composition to prepare a mixture, the compatibility, dispersibility, and reactivity can be improved.Furthermore, the mixture or the cured product of the mixture can be adjusted to be soft.

[0044] The organic group 2 may be an aliphatic group, an aromatic group, or may have both an aliphatic group and an aromatic group. The organic group 2 present in one molecule of the oxygen-absorbing compound may be of one type or of two or more types. The organic group 2 is preferably a group containing a structural part derived from an isocyanate-based compound and / or a hydroxyl-containing compound. The structural portion derived from a group-containing compound also includes a structural portion derived from a reaction product of an isocyanate compound and a hydroxyl group-containing compound.

[0045] (Isocyanate compounds) Examples of isocyanate compounds from which the organic group 2 is derived include tetramethylene diisocyanate, hexamethylene diisocyanate, lysine diisocyanate, isophorone diisocyanate, norbornane diisocyanate, xylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, phenylene diisocyanate, diphenylether diisocyanate, hydrogenated diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate, and their trimethylolpropane adducts, biuret bodies, allophanate bodies, isocyanurate bodies (trimers), and various derivatives thereof. Among these, biuret bodies of toluene diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate are preferred. In the present invention, one or more types selected from the group consisting of these isocyanate compounds can be used as the origin of the structural portion of the monovalent and / or divalent or higher hydrocarbon group. When two or more types are used, two types may be used in the same molecule of the oxygen-absorbing compound, or molecules of the oxygen-absorbing compound having different types may be mixed.

[0046] The number average molecular weight of the isocyanate compound is preferably 100 to 10,000, more preferably 160 to 5,000. If the number average molecular weight is smaller than the above range, it is likely to precipitate when mixed with a resin or a resin composition. If the number average molecular weight is larger than the above range, it is likely to require a large amount of dilution solvent to be contained when mixed with a resin or a resin composition because the viscosity of the mixture increases, making it difficult to obtain a thick film or layer, and coating suitability is likely to deteriorate.

[0047] (Hydroxy group-containing compound) The hydroxyl group-containing compound is a compound from which the above organic group 2 is derived, and has two or more hydroxyl groups. Examples of the hydroxyl group-containing compound include polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof. Among these, polyether polyols and polyolefin polyols are preferred. In order to prevent odor generation, the hydroxyl group-containing compound is preferably one that does not have a double bond in the aliphatic chain of the main skeleton or one that has two hydroxyl groups. Compounds that have a hydroxyl group at the end are preferred because they are more readily available, but they do not have to be at the end. In the present invention, one or more types selected from the group consisting of these can be used as the hydroxyl group-containing compound from which the organic group 2 is derived. When two or more types are used, two types may be used in the same molecule of the oxygen-absorbing compound, or molecules of the oxygen-absorbing compound having different types may be mixed. The number average molecular weight of the hydroxyl group-containing compound is preferably 500 to 10,000, more preferably 750 to 5,000, and even more preferably 1,000 to 3,000. If the number average molecular weight is smaller than the above range, it is likely to precipitate when mixed with a resin or a resin composition. If the number average molecular weight is larger than the above range, it is likely to require a large amount of dilution solvent to be contained when mixed with a resin or a resin composition because the viscosity of the mixture increases, making it difficult to obtain a thick film or layer, and coating suitability is likely to deteriorate.

[0048] Polyhydric alcohols Polyhydric alcohols are monomers having two or more hydroxyl groups. Specific examples of polyhydric alcohols include diols such as ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,3-butanediol, 1,6-hexanediol, cyclohexanedimethanol, 1,8-octanediol, 1,9-nonanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2-methyl-1,3-propanediol, 2,2,4-trimethyl-1,3-pentanediol, 2,4-diethyl-1,5-pentanediol, 1,12-octadecanediol, and 2,2'-oxydiethanol, as well as glycerin, mannitol, and sorbitol. Among the above, ethylene glycol is preferred in terms of oxygen absorption.

[0049] Polyolefin polyol The polyolefin polyol is a polyolefin resin having two or more hydroxyl groups. Specific examples of polyolefin polyols include those whose main skeleton is a polyolefin such as polyethylene, polypropylene, polybutylene, polybutadiene, hydrogenated polybutadiene, polyisoprene, hydrogenated polyisoprene, ethylene-vinyl acetate copolymer, ethylene-ethyl (meth)acrylate copolymer, ethylene-(meth)acrylic acid copolymer, and ethylene-propylene copolymer, and which have a hydroxyl group. Among these, those having an ethylene-vinyl acetate copolymer or hydrogenated polyisoprene as the main skeleton are particularly preferred.

[0050] Polyether polyol Polyether polyol is a polyether resin having two or more hydroxyl groups. Polyether polyols are obtained, for example, by dehydration condensation of the above-mentioned polyhydric alcohols or polyolefin polyols, and have a polyether structure in the main skeleton and a hydroxyl group. Specific examples of polyether polyols include diethylene glycol, triethylene glycol, dipropylene glycol, polyethylene ether diol, polypropylene ether diol, polybutylene ether diol, glycerin-modified polyether polyols, etc. Among these, polypropylene ether diol is particularly preferred.

[0051] Polyester polyol The polyester polyol is a polyester resin having two or more hydroxyl groups. The polyester polyols are obtained, for example, by esterification reaction between various polyvalent carboxylic acids or derivatives thereof and the above-mentioned polyhydric alcohols, polyolefin polyols, polyether polyols, etc., and have a polyester structure in the main skeleton and hydroxyl groups. Specific examples of polycarboxylic acids include adipic acid, phthalic acid, isophthalic acid, terephthalic acid, maleic acid, fumaric acid, succinic acid, oxalic acid, malonic acid, pimelic acid, azelaic acid, sebacic acid, suberic acid, glutaric acid, 1,4-cyclohexanedicarboxylic acid, and trimellitic acid. Derivatives of these polycarboxylic acids include esters, acid anhydrides, and acylation products. Among the above, polyester polyols using two or more kinds of polyhydric alcohols and two or more kinds of polyvalent carboxylic acids in combination are preferred in order to reduce crystallinity.

[0052] Polycarbonate polyol Polycarbonate polyol is a polycarbonate resin having two or more hydroxyl groups. Polycarbonate has a polyol-derived portion in the main skeleton, and this polyol-derived portion may be derived from the above-mentioned polyhydric alcohols, polyolefin polyol, polyether polyol, polyester polyol, or the like. Among these, polycarbonates that use two or more types of polyhydric alcohol in combination to reduce crystallinity are Carbonate polyols are preferred.

[0053] Poly(meth)acrylic acid ester polyol The poly(meth)acrylate polyol is a (meth)acrylate (co)polymer having two or more hydroxyl groups. Poly(meth)acrylic acid ester polyol can be obtained, for example, by using a hydroxyl group-containing monomer such as 2-hydroxyethyl methacrylate or a (meth)acrylic acid ester having a hydroxyl group synthesized from one (meth)acrylic acid or a derivative thereof and one diol, and polymerizing the hydroxyl group-containing monomer with itself or copolymerizing it with a (meth)acrylic acid ester not having a hydroxyl group. As the diol used in synthesizing the (meth)acrylic ester having a hydroxyl group, the above-mentioned diols, polyolefin polyol, polyether polyol, etc. can be used. Among these, a poly(meth)acrylic acid ester copolymer using 2-hydroxyethyl methacrylate is preferred.

[0054] Phenoxy resin Phenoxy resin is a resin obtained by reacting a polyhydric phenol compound with a polyhydric epoxy compound, and has a structure in which an aliphatic hydroxyl group is generated at the bond formed by reaction between an aromatic hydroxyl group and an epoxy group. As the phenoxy resin, those obtained by reacting a bisphenol with a diglycidyl etherified bisphenol are readily available and are common. Examples of the polyhydric phenol compound include bisphenol A and bisphenol F, and examples of the polyfunctional epoxy compound include bisphenol A diglycidyl ether and bisphenol F diglycidyl ether. Among these, phenoxy resins using bisphenol A are preferred. The terminal of the phenoxy resin may be an aromatic hydroxyl group or an epoxy group.

[0055] · Urethane chain-extended polyol The urethane chain-extended polyol is a polyol having two or more hydroxyl groups, which is obtained by extending the above-mentioned hydroxyl group-containing compound with a urethane chain. The urethane chain-extended polyol can be obtained, for example, by polymerizing the above-mentioned various hydroxyl group-containing compounds with the above-mentioned isocyanate-based compounds to extend the urethane chain. If necessary, diamines or amino alcohols may be used in combination for polymerization. Among the above, urethane chain-extended polyols obtained by reacting the above-mentioned various hydroxyl group-containing compounds having hydroxyl groups at both ends with a diisocyanate compound are preferred.

[0056] (Specific examples of oxygen absorbing compounds) Specific examples of the oxygen-absorbing compound are given below. 3a,4,5,6,7,7a-Hexahydro-4,7-methano-1H-indenol represented by formula (1), 3a,4,5,6,7,7a-hexahydro-4,7-methano-1H-indenamine represented by formula (1-b), and 3a,4,5,6,7,7a-hexahydro-4,7-methano-1H-inden-1-ol represented by formula (1-c) are examples of oxygen absorbing compounds each having one unsaturated five-membered ring and one organic group 1, and the organic group 1 has a hydroxyl group or an amino group as a functional group having active hydrogen. [ka] [ka] [ka]

[0057] The oxygen absorbing compound represented by formula (2) is, for example, a compound having a hydroxyl group, which is a functional group having an active hydrogen on organic group 1 of the oxygen absorbing compound represented by formula (1), and an isocyanate compound R 1 (NCO) a The isocyanate group of the hydroxyl group reacts with the The active hydrogen is replaced, and a number of the unsaturated five-membered rings and the organic group 1 are R 1 It can be obtained by combining through It is an oxygen absorbing compound that can [ka] (In the formula, a is a number of 1 or more, and R 1 is an organic group having one or more carbon atoms, and It may contain an alkylene and / or phenylene structure, and further contain a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof.

[0058] The oxygen absorbing compound represented by formula (5) is a compound represented by formula (2) in which a=2 and R 1 For example, the isocyanate compound OCN-R 4 -NCO and hydroxyl group-containing compound HO-R 5 Oxygen absorption when the group is derived from -OH and contains a structural part generated by the reaction of the two It is a volatile compound. [ka] (In the formula, f is a number equal to or greater than 0, and R 4 and R 5 Each of the above is an organic group having one or more carbon atoms, containing at least an alkylene and / or phenylene structure, and further may contain a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof.

[0059] The oxygen-absorbing compound represented by formula (3) may be, for example, 1Isocyanate The oxygen-absorbing compound is derived from a nate compound and a hydroxyl group-containing compound, contains a structural portion formed by the reaction of the two, and contains hydroxyl groups as a result of residual excess hydroxyl groups or chemical modification. [ka] (In the formula, b and c are each a number equal to or greater than 1; R 2 is an organic group having one or more carbon atoms, The polyol may contain at least an alkylene and / or phenylene structure, and may further contain a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof.

[0060] The oxygen-absorbing compound represented by formula (4) may be, for example, 1 Isocyanate The oxygen-absorbing compound is derived from a hydroxyl group-containing compound and a carboxylate-based compound, contains a structural part formed by the reaction of the two, and contains an isocyanate group due to residual excess isocyanate groups or chemical modification. [ka] (wherein, d and e are each a number equal to or greater than 1; R 3 is an organic group having one or more carbon atoms, The polyol may contain at least an alkylene and / or phenylene structure, and may further contain a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof.

[0061] [Oxidation promotion catalyst] The oxidation-promoting catalyst is a compound that promotes the action of the oxygen-absorbing compound absorbing oxygen molecules and being oxidized. Examples of the oxidation-promoting catalyst include peroxides and compounds containing cations made of transition metals. Specific examples of the peroxide include hydrogen peroxide. The compound containing a cation made of a transition metal is preferably a metal soap made of a transition metal-containing compound capable of releasing a cation or complex of a transition metal atom and an anion or ligand made of a fatty acid. The transition metal is preferably cobalt, manganese, iron, nickel, copper, etc., and the anion or ligand is preferably stearic acid, naphthenic acid, octylic acid, acetylacetonate, etc. Preferred are anions or ligands consisting of: The oxidation-promoting catalyst may be a metal soap formed by combining a cation made of one or more transition metals selected from the group consisting of the above transition metals with an anion made of one or more fatty acids selected from the group consisting of the above long-chain fatty acids. Specific compounds include cobalt octylate, cobalt acetylacetone (II), cobalt acetylacetone (III), manganese acetylacetone (III), and iron acetylacetone (III).

[0062] [Denaturant] The modifier is a compound having a functional group that reacts with the oxygen absorbing compound when the oxygen absorbing compound has a functional group, and various reactive monomers and resins can be used. By including a modifier in the oxygen-absorbing adhesive composition, it is possible to bond the oxygen-absorbing compound to other components in the oxygen-absorbing adhesive composition, to adjust the content of the oxygen-absorbing compound in the oxygen-absorbing adhesive composition, and to adjust the hardness of the cured product of the oxygen-absorbing adhesive composition.

[0063] For example, when the oxygen absorbing compound has a hydroxyl group or an isocyanate group, a modifying agent made of an isocyanate compound and / or a hydroxyl group-containing compound can be used. When the oxygen-absorbing adhesive composition is a urethane-based one, the equivalent ratio NCO / OH of the oxygen-absorbing adhesive composition is preferably 0.5 or more and 8 or less. If it is less than the above range, the curing of the oxygen-absorbing adhesive composition may be insufficient, and sufficient lamination strength (adhesive strength) may not be obtained, whereas if it is greater than the above range, the pot life of the oxygen-absorbing adhesive composition may be too short.

[0064] (Isocyanate compounds for use as modifiers) The isocyanate compound for the modifier can be the isocyanate compound used in the synthesis of the oxygen absorbing compound, and any of aromatic isocyanates, aliphatic isocyanates, and urethane chain-extended isocyanates thereof can be used. In addition, in order for the oxygen absorbing adhesive composition to harden, it is preferable to use one having two or more isocyanate groups in one molecule. However, it is also possible to use an isocyanate compound having one isocyanate group in one molecule in the range that does not inhibit the sufficient effect of the oxygen absorbing adhesive composition. As the isocyanate compound having two or more isocyanate groups in one molecule, a biuret form of hexamethylene diisocyanate is particularly preferred.

[0065] Specific examples of isocyanate compounds include tetramethylene diisocyanate, hexamethylene diisocyanate, lysine diisocyanate, isophorone diisocyanate, norbornane diisocyanate, xylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, phenylene diisocyanate, diphenylether diisocyanate, polymethylene polyphenyl polyisocyanate, and their trimethylolpropane adducts, biuret compounds, allophanate compounds, isocyanurate compounds (trimers), and various derivatives thereof. Among these, the biuret compounds of toluene diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate are preferred.

[0066] (Hydroxyl-containing compounds for use as modifiers) The hydroxyl group-containing compound for the modifier can be the hydroxyl group-containing compound used in the synthesis of the oxygen absorbing compound, and any of aromatic hydroxyl group-containing compounds, aliphatic hydroxyl group-containing compounds, and urethane chain-extended polyols thereof can be used. In addition, in order for the oxygen absorbing adhesive composition to harden, it is preferable for one molecule to have two or more hydroxyl groups. However, A hydroxyl-containing compound having one hydroxyl group per molecule can also be used in combination within a range that does not impair the sufficient effect of the water-absorbent adhesive composition. As the hydroxyl group-containing compound having two or more hydroxyl groups in one molecule, either an aromatic hydroxyl group-containing compound or an aliphatic hydroxyl group-containing compound can be used, and either an alcohol-based or a phenol-based compound can be used. As the isocyanate compound having two or more isocyanate groups in one molecule, polyalkylene ether diols and urethane chain extended polyols of polyalkylene ether diols are particularly preferred.

[0067] [Dilution solvent] The dilution solvent is not particularly limited as long as it uniformly dissolves or disperses the oxygen-absorbing compound and the oxidation-promoting catalyst, makes the oxygen-absorbing adhesive composition uniform, and is compatible with the dry lamination process. For example, an ester-based dilution solvent, a ketone-based dilution solvent, a hydrocarbon-based dilution solvent, etc. can be used. Specific examples of the ester-based diluent solvent include ethyl acetate, butyl acetate, etc., specific examples of the ketone-based diluent solvent include methyl ethyl ketone, etc., and specific examples of the hydrocarbon-based diluent solvent include toluene, etc. Among these, ethyl acetate is easy to use and is preferable.

[0068] [Various additives] The oxygen-absorbing adhesive composition may contain various additives as necessary. For example, curing accelerators, curing regulators for extending the pot life, antioxidants for suppressing a decrease in oxygen absorbing properties during storage or use of the oxygen absorbing adhesive composition and before the contents are placed in a package, adhesion aids, tackifiers, leveling agents, ultraviolet absorbers, defoamers, coloring pigments, and extender pigments may also be added.

[0069] (Cure accelerator) There are no particular limitations on the curing accelerator that can be used as long as it accelerates the curing reaction of the oxygen-absorbing adhesive composition. Specific examples of the curing accelerator include metal-containing compounds such as dibutyltin dilaurate, dibutyltin diacetate, dioctyltin dilaurate, dibutyltin dimaleate, tetrabutyl titanate, and tetraisopropyl titanate, and tertiary amines such as 1,8-diaza-bicyclo(5,4,0)undecene-7, 1,5-diazabicyclo(4,3,0)nonene-5, and triethanolamine. One or more types selected from the group consisting of these can be used.

[0070] (hardening regulator) When the pot life of the oxygen-absorbing adhesive composition is shortened due to the oxidation-promoting catalyst contained therein, the pot life can be extended by using a cure regulator in combination. Specific examples of the hardening regulator include phosphoric acids, such as orthophosphoric acid, metaphosphoric acid, polyphosphoric acid, and ester derivatives thereof. One or more selected from the group consisting of these can be used. The amount of reaction regulator added is preferably 200 ppm or more and 400 ppm or less based on the resin component of the oxygen-absorbing adhesive composition. If the amount is less than this range, it is difficult to obtain the effect of extending the pot life, and if the amount is more than this range, there is a risk that the curing of the oxygen-absorbing adhesive composition is inhibited.

[0071] (Antioxidants) The oxygen-absorbing adhesive composition is prevented from deteriorating in oxygen absorption during storage and use, and also during processes before a package made using the oxygen-absorbing adhesive composition contains contents. In order to maintain high oxygen absorbing properties after the contents are contained, the oxygen absorbing adhesive composition may contain an antioxidant. Specific examples of the antioxidant include phenols, lactones, thioethers, gallic acids, ascorbic acid, erythorbic acid, catechin, dibutylhydroxytoluene, tocopherol, citric acid, butylhydroxyanisole, phosphite, hindered amines, and aromatic amines. One or more selected from the group consisting of these antioxidants can be used. In addition, when it is assumed that heat or light is used as a trigger for expressing oxygen absorbing ability, it is preferable to use an antioxidant having low heat resistance and light resistance, such as ascorbic acid or tocopherol, and it is not preferable to use an antioxidant having high heat resistance and light resistance, such as a phenol-based antioxidant. The amount of the antioxidant added is preferably 10 ppm or more and 10000 ppm or less relative to the oxygen absorbing compound. If the amount is less than the above range, the antioxidant effect is likely to be insufficient, and if the amount is more than the above range, there is a risk that the oxygen absorbing ability will decrease.

[0072] (Adhesive assistant) As an adhesion aid for aiding adhesive strength, a silane coupling agent is preferred. Examples of the silane coupling agent include γ-glycidoxypropyltrialkoxysilane, γ-methacryloxypropyltrialkoxysilane, γ-glycidoxypropylmethyldialkoxysilane, β-(3,4-epoxycyclohexyl)ethyltrialkoxysilane, γ-aminopropyltrialkoxysilane, γ-aminopropylmethyldialkoxysilane, N-(β-aminoethyl)-γ-aminopropyltrialkoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldialkoxysilane, N-butyl-3-amino-2-methylpropyltrialkoxysilane, γ-mercaptopropyltrialkoxysilane, and γ-mercaptopropylmethyldialkoxysilane. The alkoxy group is preferably a methoxy group or an ethoxy group, and one or more selected from the group consisting of these can be used.

[0073] (tackifier) Examples of the tackifier include paraffin wax, polyethylene wax, rosin, rosin glycerin ester, terpene, and alkylphenol. One or more types selected from the group consisting of these can be used.

[0074] (Leveling agent) The leveling agent may be an acrylic polymer-based agent, a modified silicone-based agent, an acetylene diol-based agent, or the like. One or more types selected from the group consisting of these may be used.

[0075] (UV absorber) Examples of the ultraviolet absorbing agent include benzotriazole-based, hydroxyphenyltriazine-based, and hindered amine-based agents, and one or more types selected from the group consisting of these may be used.

[0076] (Antifoaming agent) The antifoaming agent may be a surfactant, polyether-modified silicone oil, or the like, and one or more selected from the group consisting of these may be used.

[0077] (Color pigments) Color pigments include organic pigments such as anthraquinone, diketopyrrolopyrrole, perylene maroon, carbon black, dioxazine, perylene, benzimidazolone, isoindolinone, isoindoline, phthalocyanine, and indanthrene, as well as yellow iron oxide and red Examples of the inorganic pigment include iron oxide, azomethine copper complex, titanium oxide, silicon oxide, and the like. One or more pigments selected from the group consisting of these can be used.

[0078] (Extender pigment) The extender pigment is a white or colorless pigment that is used as an extender or as an adjuster for coloring power, gloss, strength, usability, etc. Specific examples include inorganic pigments such as barium sulfate, barium carbonate, calcium carbonate, magnesium oxide, magnesium carbonate, magnesium hydroxide, barium titanate, calcium hydroxide, calcium sulfite, calcium sulfate, calcium oxide, calcium silicate, titanium oxide, silica, zeolite, and talc, and one or more types selected from the group consisting of these can be used.

[0079] <<Method for preparing oxygen-absorbing adhesive composition>> The oxygen-absorbing adhesive composition can be produced by mixing all of the components, such as the oxygen-absorbing compound, the oxidation-promoting catalyst, and, if necessary, the modifier, the diluting solvent, the various additives, etc. Alternatively, the oxygen-absorbing adhesive composition can be produced by mixing the oxygen-absorbing compound, the oxidation-promoting catalyst, and, if necessary, the modifier, the diluting solvent, the various additives, etc., with an existing adhesive composition. The method for carrying out the above mixing and the order in which the components are mixed are not particularly limited, and the method and mixing order used in preparing a general adhesive composition can be applied. Specific mixing methods include a method of dissolving in a solvent and mixing, and a method of melt-kneading. In this case, it is preferable to adjust the heating temperature in order to increase the solubility or dispersibility.

[0080] <<Method of using the oxygen-absorbing adhesive composition>> There are no particular limitations on the method of using the oxygen-absorbing adhesive composition, and any method for using it as an adhesive can be used. For example, there may be mentioned a non-solvent type lamination method in which the coating is heated to obtain an appropriate viscosity, and a dry lamination method in which a dilution solvent or other compounded adhesive is added to adjust the coating viscosity to an appropriate level. When forming an adhesive layer using the oxygen absorbing adhesive composition, the coating amount is 2 to 5 g / m 2 is preferable, and 3 to 5 g / m 2 If the amount is less than the above range, sufficient oxygen absorbency may not be obtained, whereas if the amount is more than the above range, the oxygen absorbency does not change significantly, leading to a cost disadvantage, which is not preferable.

[0081] A laminate obtained by forming and bonding an adhesive layer using the oxygen-absorbing adhesive composition is preferably aged at 20° C. or higher and 50° C. or lower for 2 days or higher and 5 days or lower. In addition, in order not to decrease the oxygen absorption property of the laminate, it is preferable to carry out the aging at a temperature as low as possible or in an inert gas atmosphere. When storing the produced laminate, it is preferable to store it at 10° C. or below or in an inert gas atmosphere in order not to decrease the oxygen absorbing property of the laminate.

[0082] About objects that can be glued There are no particular limitations on the objects to which the oxygen-absorbing adhesive composition can be adhered, and for example, it can be adhered to resin molded products, resin films, paper, metals, metal foils, inorganic vapor deposition film surfaces, and inorganic oxide vapor deposition film surfaces.

[0083] Specific examples of the resin of the resin film include polyester resins such as polyethylene terephthalate (PET), polyamide resins such as various nylons, polyethylene resins, polypropylene resins, cyclic polyolefin resins, polystyrene resins, and acrylonitrile resins. Examples of suitable resins include polyolefin resins such as styrene-butadiene copolymers (AS resins), acrylonitrile-butadiene-styrene copolymers (ABS resins), and polybutene resins, polyvinyl chloride resins, polycarbonate resins, polyimide resins, polyamideimide resins, diallyl phthalate resins, silicone resins, polysulfone resins, polyphenylene sulfide resins, polyethersulfone resins, polyurethane resins, cellulose resins, poly(meth)acrylic resins, polyvinylidene chloride resins, acetal resins, and fluorine-based resins.

[0084] Specific examples of paper include strong sizing bleached or unbleached paper base materials for paper layers, or paper base materials such as pure white roll paper, kraft paper, paperboard, coated paper, processed paper, milk base paper, and the like. Specific examples of the metal foil include aluminum foil, copper foil, and stainless steel foil. A specific example of the metal of the inorganic vapor deposition layer is aluminum. Specific examples of inorganic oxides in the inorganic vapor deposition layer include silica, alumina, indium tin oxide, zinc oxide, tin oxide, titanium oxide, zirconium oxide, vanadium oxide, barium oxide, chromium oxide, silicon nitride, silicon carbide, etc. Among these, silica and alumina are preferred.

[0085] <Sealant layer> The sealant layer may be composed of a single layer, or may be composed of two or more layers having the same or different compositions. Since the sealant layer is heat-sealed to the lid material forming the blister packaging container, it preferably contains a resin having heat-sealing properties with the lid material and has heat-sealing properties. In addition, the sealant layer can also have easy-opening properties (easy peeling properties). In order to provide easy opening properties, the sealant layer preferably has an easy peel layer as the outermost layer of the sealant layer, and further has a support layer for supporting the easy peel layer. The easy-peel layer can provide easy opening by, for example, causing cohesive failure of the easy-peel layer having a sea-island structure and peeling at the sea-island interface, or by having appropriate adhesive strength. In the case of an easy peel layer having a sea-island structure, the easy peel layer is a layer made of a blend polymer containing two or more mutually incompatible resins. In order to have heat sealability, it is preferable that the sea structure contains a resin having heat sealability. The blended polymers are not intentionally reacted with each other. Since they are incompatible with each other, they form a sea-island structure. Since the bonds at the sea-island interface are weak due to the incompatibility, peeling easily occurs at the sea-island interface during peeling, which provides easy peeling of the easy peel layer as a whole. In the case of an easy peel layer having a suitable adhesive strength, the easy peel layer is preferably a heat sealable resin having a suitable adhesive strength, or a blend of a resin having a strong adhesive strength and a heat sealable resin having a weak adhesive strength, and further, the adhesive strength can be adjusted by adding an adhesive resin or a filler. In addition, the types of resins to be blended and their blend ratios can be adjusted depending on the composition of the resin on the surface of the molded part to be heat sealed. The supporting layer for supporting the easy peel layer preferably contains a heat sealable resin in order to have heat sealability. Such an easily peelable sealant layer can be formed by laminating a publicly known and publicly used easy-peel film.

[0086] The sealant layer may contain any additives as long as they do not significantly impair the effects of the present invention. The additives include various resin additives that are generally used to adjust the moldability, productivity, and various physical properties of the resin film, such as antiblocking agents and slip agents. , antioxidants, pigments, flow control materials, flame retardants, fillers, ultraviolet absorbers, surfactants, etc. The thickness of the sealant layer is preferably from 10 μm to 200 μm, and more preferably from 30 μm to 100 μm.

[0087] (Heat-sealable resin) Examples of resins having heat sealability include polyolefin resins, acid-modified polyolefin resins obtained by acid-modifying polyolefin resins by graft polymerization or copolymerization with unsaturated carboxylic acids or their anhydrides such as acrylic acid, methacrylic acid, maleic acid, maleic anhydride, fumaric acid, itaconic acid, etc., polyvinyl acetate resins, poly(meth)acrylic resins, polyvinyl chloride resins, and other resins. These resins can be used alone or in combination.

[0088] (Polyolefin resin) Specific examples of polyolefin resins include polyethylene, low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, ethylene-α-olefin copolymers polymerized using a metallocene catalyst, polypropylene, ethylene-vinyl acetate copolymers, ethylene-vinyl alcohol copolymers, ionomer resins, ethylene-acrylic acid copolymers, ethylene-ethyl acrylate copolymers, ethylene-methacrylic acid copolymers, ethylene-methyl methacrylate copolymers, ethylene-propylene copolymers, methylpentene (co)polymers, butene (co)polymers, ethylene-acrylic acid copolymers, ethylene-methacrylic acid copolymers, and cyclic olefin (co)polymers such as polynorbornene. The copolymers may be random or block copolymers. Polyolefin resins are classified into, for example, polyethylene resins and polypropylene resins depending on the skeleton of the monomer used in the synthesis of the polyolefin, and may be copolymers. In the present invention, the term "polyethylene resin" is added as a general term for various types, and for example, polyethylene resin is also used as a general term for various types of polyethylene. Polyolefins produced by polymerizing α-olefins such as ethylene, propene, 1-butene, 1,3-butadiene, and 1-hexene as raw materials are called polyethylene-based resins, polypropylene-based resins, polybutylene-based resins, polybutadiene-based resins, polyhexene-based resins, and the like, respectively. Common polymerization methods include, for example, a high-pressure method for low-density polyethylene, and a low-pressure polymerization method (gas phase polymerization using a Ziegler-Natta catalyst or liquid phase polymerization using a metallocene catalyst), slurry method, solution method, gas phase polymerization method, etc. for linear low-density polyethylene.

[0089] (Method of forming sealant layer) The method for forming the sealant layer is not particularly limited, and any conventionally known method for laminating a sealant layer can be used. A sealant film consisting of one or more layers for the sealant layer may be prepared in advance, and the sealant film may be laminated by adhering it to other layers constituting the laminate via an adhesive, etc. The sealant film may be prepared by melt-extruding one or more resin compositions and forming them into a film by an inflation method, or by melt-extruding onto a roll and constricting it by an extrusion method using a T-die molding or the like to form a film. Here, it is preferable to subject one side of the prepared sealant film to a corona treatment, and then laminate the film by adhering the corona-treated side to the side to be laminated. Alternatively, the resin composition for forming the sealant layer may be melted, melt (co)extruded, and poured onto the layers to be laminated, and a sealant layer consisting of one or more layers may be laminated onto the other layers that make up the laminate by an extrusion method using a T-die molding method using a feed block method or a multi-manifold method. In either method, a multi-layer sealant film can be produced by co-melt extrusion using resin compositions of the same or different compositions.

[0090] ≪Base material layer≫ As the material for the substrate layer, for example, a general known resin film having excellent mechanical, physical, chemical and other properties as a basic material for forming molded parts of blister packaging containers, particularly having strength, toughness and heat resistance, can be used. Furthermore, various paper substrates can be used, and a resin film and a paper substrate can be used in combination. The substrate layer may be composed of one layer, or may be composed of two or more layers of the same or different composition laminated by any lamination means. The thickness of the base layer can be appropriately set by those skilled in the art, but for the purpose of imparting appropriate strength and stiffness to the laminate, a thickness of, for example, 5 to 500 μm is preferable, but varies depending on the rigidity of the resin film used. For example, in the case of a biaxially oriented PET film, the thickness is preferably 5 to 100 μm, and in the case of a PPVC·PVDC composite film, the thickness is preferably 150 to 350 μm.

[0091] Specific examples of the resin contained in the resin film include polyesters such as polyethylene terephthalate (PET) and polyethylene naphthalate, polyolefins such as polypropylene, and polyvinyl chloride (PVC). The resin film may be either an unstretched film or a uniaxially or biaxially stretched film. Among the above, biaxially oriented PET film and PVC·PVDC composite film are preferably used. Furthermore, in order to improve the oxygen barrier properties, moisture resistance, and adhesion to the lid material sheet, it is also possible to use a multilayer resin film in which polyvinylidene chloride (PVDC) is laminated onto the above-mentioned resin film by coating, or a multilayer resin film laminated with polyethylene, polypropylene, cyclic olefin copolymer, fluororesin, etc.

[0092] The paper base material can impart shapeability, flex resistance, rigidity, etc., and for example, a strong sizing bleached or unbleached paper base material for a paper layer, or a paper base material such as pure white roll paper, kraft paper, paperboard, coated paper, processed paper, milk base paper, etc. can be used. The paper base material has a basis weight of approximately 30 g / m 2 ~600g / m 2 The preferred basis weight is about 50 g / m 2 ~450g / m 2 The order is more preferable.

[0093] If necessary, plastic compounding agents and additives such as lubricants, crosslinking agents, antioxidants, UV absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, and pigments may be added to the resin film used for the base layer for the purpose of improving or modifying processability, heat resistance, weather resistance, mechanical properties, dimensional stability, oxidation resistance, slipperiness, release properties, flame retardancy, mildew resistance, electrical properties, strength, and the like. The amount of these additives may be arbitrarily added depending on the purpose as long as it does not adversely affect other performance properties. The substrate layer can be laminated with other layers via an adhesive layer. Furthermore, if necessary, in order to strengthen the adhesive strength between the substrate layer and the adhesive layer, the surface of the substrate layer that contacts the adhesive can be previously subjected to physical surface treatment such as corona discharge treatment, ozone treatment, plasma treatment, glow discharge treatment, sandblasting treatment, etc., or chemical surface treatment such as oxidation treatment using chemicals.

[0094] ≪Printing layer≫ The printing layer is a layer of design patterns such as letters, numbers, figures, symbols, pictures, patterns, etc., for decoration, display of contents, display of expiration date, display of manufacturer, seller, etc., and for providing aesthetic impression. It provides a visual indication of the turn and allows for the creation of desired design patterns. The printed layer is preferably formed on one or both sides of the base layer by a printing method such as gravure printing or flexographic printing. The printed layer may be provided on the entire surface of the printed surface, or may be provided on only a part of the surface. By forming the printed layer inside the oxygen-absorbing laminate, the adhesion of the printed layer can be improved, and the ink on the printed layer can be prevented from being rubbed off or peeled off due to external impact or friction. When the oxygen-absorbing packaging material for molded parts has a printed layer, the layer that is on the outer side of the printed layer when the container is formed is preferably transparent so that the printed layer can be visually confirmed.

[0095] <General-purpose adhesive layer> A general-purpose adhesive layer or anchor coat layer may be included between each of the layers constituting the oxygen-absorbing laminate. The general-purpose adhesive layer may be, for example, a layer (extruded resin layer) formed by a (co)extrusion lamination method in which an adhesive resin composition is melt-extruded, a T-die (co)extrusion method, or the like, or may be a layer (dry laminate layer) formed by dry lamination using a dry laminate adhesive. Examples of the resin contained in the adhesive resin composition include polyolefin resins, acid-modified polyolefin resins obtained by acid-modifying polyolefin resins by graft polymerization or copolymerization with unsaturated carboxylic acids or their anhydrides such as acrylic acid, methacrylic acid, maleic acid, maleic anhydride, fumaric acid, itaconic acid, etc., polyvinyl acetate resins, poly(meth)acrylic resins, polyvinyl chloride resins, etc. These resins can be used alone or in combination.

[0096] Specific examples of polyolefin resins include polyethylene, low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, ethylene-α-olefin copolymers polymerized using a metallocene catalyst, polypropylene, ethylene-vinyl acetate copolymers, ethylene-vinyl alcohol copolymers, ionomer resins, ethylene-acrylic acid copolymers, ethylene-ethyl acrylate copolymers, ethylene-methacrylic acid copolymers, ethylene-methyl methacrylate copolymers, ethylene-propylene copolymers, methylpentene (co)polymers, butene (co)polymers, polyisoprene, ethylene-acrylic acid copolymers, ethylene-methacrylic acid copolymers, and cyclic olefin (co)polymers such as polynorbornene. The copolymers may be random or block copolymers.

[0097] The polyolefin resin may contain a resin derived from fossil fuels and / or a resin synthesized using raw materials derived from plants. By containing a polyolefin resin derived from plants synthesized using raw materials derived from plants, the environmental load can be reduced. The plant-derived polyolefin resin can be selected with an appropriate density and MFR depending on the physical properties of the fossil fuel-derived polyolefin resin used in combination and the application of the sealant layer. The content of the plant-derived polyolefin resin in the sealant layer A or B is preferably 40% by mass or more and 100% by mass or less. If it is less than the above range, the biomass degree of the sealant layer A or B or the laminate will be low, and the effect of reducing the environmental load will be reduced. The biomass ratio of the oxygen absorbing laminate of the present invention is preferably 10% or more and 50% or less. If it is less than the above range, the reduction in environmental load is small, and if it is more than the above range, the hand-tearability and drop impact resistance of the laminate are likely to decrease. The biomass degree of the sealant layer A or B is preferably 10% or more and 20% or less. If it is less than the above range, the reduction in environmental load is small, and if it is more than the above range, the hand-tearability and drop impact resistance of the laminate tend to decrease. When the sealant layer A or B has a multi-layer structure, the sealant layer A or B is made of plant-derived There may be a layer containing the polyolefin resin and a layer not containing the plant-derived polyolefin resin. For example, it is preferable that the outer surface layer of the sealant layer A or B, which is the outermost surface of the laminate, does not contain a plant-derived polyolefin resin. Furthermore, when the sealant layer A or B has a multi-layer structure of three or more layers, it is preferable that the outer surface layer, which is the outermost surface of the laminate, and the inner surface layer in contact with other layers do not contain a plant-derived polyolefin resin, and the inner layer contains a plant-derived polyolefin resin.

[0098] Polyolefin resins are classified into, for example, polyethylene resins and polypropylene resins depending on the skeleton of the monomer used in the synthesis of the polyolefin, and may be copolymers. In the present invention, the term "polyethylene resin" is added as a general term for various types, and for example, polyethylene resin is also used as a general term for various types of polyethylene. Polyolefins produced by polymerizing α-olefins such as ethylene, propene, 1-butene, 1,3-butadiene, and 1-hexene as raw materials are called polyethylene-based resins, polypropylene-based resins, polybutylene-based resins, polybutadiene-based resins, polyhexene-based resins, and the like, respectively.

[0099] The general-purpose adhesive layer may contain additives such as antioxidants, ultraviolet absorbers, light stabilizers, antistatic agents, antiblocking agents, flame retardants, crosslinking agents, and colorants, as long as the additives do not impair the properties of the present invention. The thickness of the general-purpose adhesive layer is not particularly limited, but is preferably 1 g / m 2 Over 20g / m 2 The thickness of the extruded resin layer is preferably 1 μm or less, or 1 μm or more and 20 μm or less. By setting the numerical value within the above range, it is possible to obtain a stable adhesive strength. In addition, examples of dry lamination adhesives that can be used to form the general-purpose adhesive layer formed by dry lamination include two-component curing urethane adhesives, polyester urethane adhesives, polyether urethane adhesives, acrylic adhesives, polyester adhesives, polyamide adhesives, polyvinyl acetate adhesives, epoxy adhesives, rubber adhesives, and others.

[0100] The anchor coat layer is a layer formed by applying and drying an anchor coat agent, and can improve the adhesion between adjacent layers. The anchor coating agent may be any resin having a heat resistant temperature of 135° C. or higher, such as a vinyl modified resin, an epoxy resin, a urethane resin, a polyester resin, or a polyethyleneimine. Among the above, a curable anchor coating agent that contains a polyacrylic or polymethacrylic resin (polyol) having two or more hydroxyl groups in one molecule as a base agent and an isocyanate compound as a curing agent is particularly preferred. A silane coupling agent may also be used in combination, and nitrocellulose may also be used in combination to improve heat resistance. The thickness of the anchor coat layer is not particularly limited, but is preferably, for example, 0.05 μm or more and 1 μm or less.

[0101] <Functional layer> Examples of functional layers include layers made of resins that have barrier properties against oxygen gas, water vapor, etc., and / or have low adsorption of fragrance ingredients contained in the contents to be filled and packaged, and thus have excellent aroma retention, and further have properties that do not cause changes in taste or odor, and that can be extrusion-molded, and layers made of light-shielding materials (light-shielding layers).

[0102] Specific examples of the resin include polyacrylic resins, polymethacrylic resins, polyacrylonitrile resins, polymethacrylonitrile resins, polystyrene resins, polycarbonate resins, polyethylene terephthalate resins, and ethylene derivatives thereof. Resins in which a part of the terephthalate component and / or terephthalate component is copolymerized or modified with other di- or higher polyhydric alcohol components or dicarboxylic acid components, or polyester-based resins such as polyethylene naphthalate-based resins, polyamide-based resins, saponified ethylene-vinyl acetate copolymers, polyvinyl alcohol-based resins, polyvinyl chloride-based resins, polyvinylidene chloride-based resins, and other resins can be used. Among the above-mentioned resins, it is preferable to use a resin that has aroma retention and also has barrier properties against oxygen gas or water vapor, etc., and specifically, it is preferable to use a resin that is rich in aroma retention and barrier properties, such as a saponified ethylene-vinyl acetate copolymer, a polyamide resin, a polyacrylonitrile resin, or a polyester resin.

[0103] The resin may contain a resin derived from a fossil fuel and / or a resin synthesized using raw materials derived from plants. By containing a plant-derived resin synthesized using raw materials derived from plants, the environmental load can be reduced. Plant-derived resins with appropriate density and MFR can be selected depending on the physical properties of the fossil fuel-derived resin used in combination and the application of the functional layer. The content of the plant-derived resin in the functional layer is preferably 40% by mass or more and 100% by mass or less. If it is less than the above range, the biomass degree of the functional layer and the laminate will be low, and the effect of reducing the environmental load will be reduced. When the functional layer has a multi-layer structure, the functional layer may have a layer containing a plant-derived resin and a layer not containing a plant-derived resin. For example, it is preferable that the layer on the outer surface, which is the outermost surface of the laminate, does not contain a plant-derived resin. Furthermore, when the reinforcing layer has a multi-layer structure of three or more layers, it is preferable that the layers on both surfaces of the functional layer do not contain a plant-derived resin, and the inner layer contains a plant-derived resin.

[0104] The light-shielding layer is a layer provided to prevent ultraviolet light and / or visible light from reaching the contents. The light-shielding layer can be formed using white ink mainly composed of titanium oxide or the like, black ink mainly composed of carbon black or the like, gray ink mainly composed of aluminum paste, colorant-colored resin film made light-shielding by adding pigments or dyes or the like, metal foil, metal vapor deposition film, or the like. As described above, when a metal foil such as an aluminum foil is used as the barrier layer, the barrier layer can also function as a light-shielding layer. These light-shielding materials can be used alone or in combination of two or more. When white ink, black ink or gray ink is used, the thickness of the light-shielding layer is preferably 4 μm or more and 12 μm or less, and more preferably 5 μm or more and 9 μm or less. In the case of aluminum foil, the thickness is preferably 5 μm to 30 μm, in the case of a metal vapor deposition film, the thickness is preferably 50 Å to 3000 Å, more preferably 100 Å to 1000 Å, and in the case of a colorant-colored resin film, the thickness is preferably 5 μm to 300 μm, more preferably 10 μm to 100 μm.

[0105] <Reinforcement layer> The reinforcing layer is a layer that imparts mechanical strength, deformation resistance, drop impact resistance, pinhole resistance, heat resistance, airtightness, quality maintenance, workability, sanitation, and the like to the laminate. The reinforcing layer may be formed from any of an extrusion-formed or inflation-formed resin film, a resin coating film, synthetic paper, and the like.

[0106] Specific examples of the resin contained in the reinforcing layer include low density polyethylene, medium density polyethylene, high density polyethylene, linear low density polyethylene, polypropylene, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, ionomer resin, ethylene-ethyl acrylate copolymer, ethylene-acrylic acid or methacrylic acid copolymer, methyl ethylene, propylene copolymer, ethylene-vinyl acetate ... Known resins that can be used include but are not limited to acrylate polymers, polybutene-based resins, polyvinyl chloride-based resins, polyvinyl acetate-based resins, polyvinylidene chloride-based resins, vinyl chloride-vinylidene chloride copolymers, poly(meth)acrylic resins, polyacrylonitrile-based resins, polystyrene-based resins, acrylonitrile-styrene copolymers (AS-based resins), acrylonitrile-butadiene-styrene copolymers (ABS-based resins), polyester-based resins, polyamide-based resins, polycarbonate-based resins, polyvinyl alcohol-based resins, saponified ethylene-vinyl acetate copolymers, fluorine-based resins, diene-based resins, polyacetal-based resins, polyurethane-based resins, cellulose, nitrocellulose, and the like.

[0107] The resin may contain a resin derived from a fossil fuel and / or a resin synthesized using raw materials derived from plants. By containing a plant-derived resin synthesized using raw materials derived from plants, the environmental load can be reduced. The plant-derived resin can be selected with an appropriate density and MFR depending on the physical properties of the fossil fuel-derived resin used in combination and the application of the reinforcing layer. The content of the plant-derived resin in the reinforcing layer is preferably 40% by mass or more and 100% by mass or less. If it is less than the above range, the biomass content of the reinforcing layer and the laminate will be low, and the effect of reducing the environmental load will be reduced. When the reinforcing layer has a multi-layer structure, the reinforcing layer may have a layer containing a plant-derived resin and a layer not containing a plant-derived resin. For example, it is preferable that the outer surface layer that is the outermost surface of the laminate does not contain a plant-derived resin. Furthermore, when the reinforcing layer has a multi-layer structure of three or more layers, it is preferable that the layers on both surfaces of the reinforcing layer do not contain a plant-derived resin and the inner layer contains a plant-derived resin.

[0108] The resin film may be either unstretched or uniaxially or biaxially stretched. The thickness of the reinforcing layer is not particularly limited, but can be selected from the range of about several μm to 300 μm.

[0109] <Method of producing the oxygen absorbing laminate> A method for producing an oxygen absorbing laminate using the above-mentioned materials will be described below. The production method described below is only one example and does not limit the present invention. The layers constituting the oxygen-absorbing laminate can be laminated by any method used in the production of ordinary packaging materials, such as wet lamination, dry lamination, solventless dry lamination, extrusion lamination, T-die coextrusion molding, coextrusion lamination, inflation molding, and the like. The oxygen absorbing laminate of the present invention can also be subjected to secondary processing for the purpose of imparting surface functions such as chemical functions, electrical functions, magnetic functions, mechanical functions, friction / wear / lubrication functions, optical functions, thermal functions, and biocompatibility. Examples of secondary processing include embossing, painting, adhesion, printing, metallizing (plating, etc.), mechanical processing, surface treatment (antistatic treatment, corona discharge treatment, plasma treatment, photochromism treatment, physical vapor deposition, chemical vapor deposition, coating, etc.), etc. The laminate of the present invention can also be subjected to lamination (dry lamination and extrusion lamination), bag making, and other post-processing.

[0110] When the above lamination is performed, if necessary, the surface of each layer may be pretreated, for example, by corona treatment or ozone treatment. In addition, anchor coating agents such as isocyanate (urethane), polyethyleneimine, polybutadiene, and organic titanium, or lamination adhesives such as polyurethane, polyacrylic, polyester, epoxy, polyvinyl acetate, cellulose, and others may be optionally used. It can be used.

[0111] As long as the base layer, oxygen barrier layer, oxygen absorbing adhesive layer, and sealant layer are laminated in this order, the order in which each layer is formed and laminated may be arbitrary. For example, an example will be described in which an oxygen-absorbing laminate for a molded part having a layer structure of a substrate layer / oxygen barrier layer / oxygen-absorbing adhesive layer / sealant layer is produced. For example, first, an oxygen barrier layer is formed on the corona-treated surface of the substrate layer. Next, an oxygen-absorbing adhesive composition is applied to the laminated oxygen barrier layer, and dried as necessary to form an oxygen-absorbing adhesive layer. Then, a sealant film for the sealant layer is adhered onto the oxygen-absorbing adhesive layer to form a sealant layer. Then, an aging treatment is performed as necessary. In this manner, an oxygen absorbing laminate for molded parts can be obtained.

[0112] <<Oxygen-absorbing packaging material for blister packing containers>> The oxygen-absorbing packaging material is a packaging material for oxygen-absorbing molded parts, which is made from the oxygen-absorbing laminate for molded parts. The oxygen-absorbing packaging material may further include layers having various functions, if necessary.

[0113] <Oxygen-absorbing molded parts for blister packing containers> The oxygen-absorbing molded part of the present invention is a molded part for a blister packaging container, which is made from the oxygen-absorbing packaging material for molded parts of the present invention. In addition, added value can be added by various shape designs and printing decorations. The oxygen-absorbing molded part may be, for example, a constricted portion that constitutes the top of a blister container, or a bottom part of a PTP packaging container, which is one form of blister container, and has a recess for accommodating the contents and a flange portion for being heat-sealed to a lid part, and is, for example, in the shape of a tray.

[0114] <Method of manufacturing oxygen-absorbing molded parts for blister packaging containers> The oxygen-absorbing molded part is produced by molding the oxygen-absorbing packaging material for molded parts of the present invention into a shape and size according to the contents to be contained. Specific molding methods include, for example, sheet molding.

[0115] <Oxygen-absorbing blister packaging container> The oxygen-absorbing blister packaging container of the present invention is a blister packaging container produced using the oxygen-absorbing molded part of the present invention. For example, as shown in Fig. 3, it is a packaging container produced by combining with a lid part or the like, and may be a packaging container of various shapes, specific examples of which include a molded container and a squeezed container for ham, etc. In addition, added value can be added by various shape designs and printing decorations. One form of blister packaging container is a PTP (Press Through Package) packaging container, which is often used, for example, when storing tablet-type medicines, and the tablet can be easily taken out by applying pressure from the molded part side and breaking the lid part together with the tablet. The oxygen-absorbing blister packaging container of the present invention may be in the form of a PTP packaging container. In the oxygen-absorbing blister packaging container, the sealant layer of the oxygen-absorbing molded part is heat-sealed to the lid part, and the oxygen barrier layer is located outside the container relative to the sealant layer. The lid part is not particularly limited, but preferably has a heat seal layer for heat sealing to the molded part. The shape of the lid part is, for example, a film-like shape, and may be a shape that matches the outer periphery of the flange part of the molded part, a shape that is slightly larger than the outer periphery, or a shape that partially fits the outer periphery. The layer structure of the lid part is not particularly limited, but it is preferable that the lid part has a heat seal layer for heat sealing to the molded part, and for example, the lid part can be formed from a packaging material including a layer structure such as a PET / polyamide / easy-peel PP-based sealant layer. The oxygen-absorbing blister packaging container can accommodate contents in the recess before the lid part and the molded part are heat-sealed, and after the contents are accommodated, the flange part of the molded part and the film-like lid part are bonded by heat sealing or adhesive to protect the contents by airtight sealing. The accommodated contents can be removed by peeling off the lid part.

[0116] <Method of manufacturing oxygen-absorbing blister packaging container> The oxygen-absorbing blister packaging container can be produced, for example, by the following production method. The example given below is merely one example of the production method of the oxygen-absorbing blister packaging container of the present invention, and the present invention is not limited thereto. To produce the oxygen-absorbing blister packaging container shown in Figure 3, first, prepare the film-like lid part shown in Figure 3, mold the tray-like molded part shown in Figure 3 using the oxygen-absorbing packaging material, place the lid part on top so that the sealant layer of the lid part faces the sealant layer of the molded part, and heat seal the lid part and the molded part at the flange portion of the molded part. In the above, when the lid part is placed on the molded part, one lid part may be placed on one molded part and heat sealed, or one lid part may be placed on two or more molded parts and heat sealed. Moreover, the two or more molded parts may be cut separately or connected.

[0117] The lid part is then cut into a shape that matches the outer periphery of the flange portion of the molded part, a shape that is annularly larger than the outer periphery, or a shape that partially protrudes. As another manufacturing method, the lid part may be cut in advance into a shape that matches the outer periphery of the flange portion of the molded part, a shape that is one size larger than the outer periphery in an annular shape, or a shape that partially protrudes, and then the lid part may be placed on the molded part and heat sealed. In addition, when producing an oxygen-absorbing blister packaging container filled with a content, it is preferable to place the content in a recess of a molded part before the above-mentioned heat sealing, and then perform the above-mentioned sheet sealing. In the above, the heat sealing can be performed by a known method such as bar sealing, rotary roll sealing, belt sealing, impulse sealing, high frequency sealing, ultrasonic sealing, flame sealing, etc.

[0118] The present invention will be described in more detail below with reference to examples and comparative examples. EXAMPLES

[0119] The present invention will be described in more detail with reference to the following examples and comparative examples, but the present invention is not limited to these examples.

[0120] <Raw materials> The main raw materials used in the examples are as follows: [Raw materials for oxygen absorbing compounds] Polypropylene ether diol 1: SANNIX PP-1000, manufactured by Sanyo Chemical Industries, Ltd. Number average molecular weight: 1000. Polypropylene ether diol 2: SANNIX PK-400, manufactured by Sanyo Chemical Industries, Ltd. Number average molecular weight: 400. Hydroxyl-terminated polyisoprene 1: Poly ip, manufactured by Idemitsu Kosan Co., Ltd., number average molecular weight 2 500. ·Hydroxyl-terminated polybutadiene 1: Poly bd R15HT manufactured by Idemitsu Kosan Co., Ltd. Number average molecular weight 1200. Hydroxyl-terminated 1,2 addition polymer of 1,3-butadiene. Toluene diisocyanate 1: Coronate T-65, manufactured by Tosoh Corporation. · Oxygen absorbing compound 1: 3a,4,5,6,7,7a-hexahydro-4,7-methano-1H-inden-6-ol. · Oxidation promotion catalyst solution 1: Octope AE, manufactured by Hope Pharmaceutical Co., Ltd. A 4% ethyl acetate solution of cobalt octoate, an oxidation promotion catalyst. · Oxidation-promoting catalyst solution 2: Aceto-pe Mn(III) manufactured by Hope Pharmaceutical Co., Ltd. A 10% ethyl acetate solution of acetylacetone manganese(III), an oxidation-promoting catalyst.

[0121] [General-purpose adhesive] DL Adhesive 1: Two-component curing polyester urethane adhesive manufactured by Rock Paint Co., Ltd. [Film for base layer and barrier layer] PET film 1: Toyobo Co., Ltd. biaxially oriented PET film, E5200. Thickness: 12 μm. PVC-PVDC composite film 1: F-9459 manufactured by Mitsubishi Plastics, Inc. 240μm thick. Both surfaces are PVC layers, with a PVDC layer in the middle. Aluminum foil 1: 30μm thick aluminum foil.

[0122] [Printing layer ink] Gravure ink 1: Finart manufactured by DIC Graphics Corporation.

[0123] [Sealant layer film] LLDPE film 1: N-165 manufactured by Aicello Co., Ltd. Non-oriented LLDPE film. Thickness: 50 μm.

[0124] <Preparation of raw material solutions> (Synthesis of polyol 1 and preparation of polyol solution 1) The following raw materials were added to a flask equipped with a nitrogen inlet tube, a stirrer, a rectification column, and a condenser, and dehydration condensation was carried out at an internal temperature of 180 to 200°C with stirring. Ethylene glycol 53.8 parts by mass Neopentyl glycol 180.3 parts by mass 1,6-Hexanediol 204.6 parts by mass Isophthalic acid 287.8 parts by mass Adipic acid 273.5 parts by mass When the acid value of the solid content of the reaction liquid reached 15 mgKOH / g, the dehydration reaction was further allowed to proceed at 200 to 240° C. while blowing in nitrogen. When the acid value of the solid content of the reaction liquid became 10 mgKOH / g or less, the internal pressure was reduced to 30 Torr and the reaction was continued. When the acid value of the solid content of the reaction liquid became 3 mgKOH / g or less, the reaction was terminated and the liquid was cooled to room temperature to obtain Polyol 1. The number average molecular weight of the resulting polyester polyol, Polyol 1, was 2,000. Next, polyol 1 was dissolved in ethyl acetate to prepare a polyol solution 1 having a solid content of 60% by mass.

[0125] (Synthesis of polyol 2 and preparation of polyol solution 2) The following raw materials were charged into a flask equipped with a nitrogen inlet tube, a stirrer, and a condenser, and the mixture was heated with stirring to carry out a reflux reaction for 6 hours. Polypropylene ether diol 1 300.0 parts by mass Polypropylene ether diol 2 250.0 parts by mass Toluene diisocyanate 1 104.0 parts by mass Ethyl acetate 163.5 parts by mass When it was confirmed by infrared absorption spectroscopy that the absorption of the isocyanate group had completely disappeared, the synthesis was terminated and the reaction mixture was cooled to obtain polyol 2. The number average molecular weight of the resulting urethane chain extended polyol, polyol 2, was 2,000. Next, polyol 2 was dissolved in ethyl acetate to prepare a polyol solution having a solid content of 60% by mass.

[0126] (Preparation of polyisocyanate solution 1) The following raw materials were added to a flask equipped with a nitrogen inlet tube, a stirrer, and a condenser and stirred to obtain a polyisocyanate solution 1 having a solid content of 60% by mass. Hexamethylene diisocyanate (buret form) 100.0 parts by mass Ethyl acetate 66.7 parts by mass

[0127] [Table 1]

[0128] <Synthesis of oxygen absorbing compound and preparation of oxygen absorbing compound solution> [Oxygen absorbing compound 2] First, the following raw materials were added to a flask equipped with a nitrogen inlet tube, a stirrer, and a condenser, and the mixture was reacted at an internal temperature of 80 to 90° C. for 8 hours with stirring. Oxygen absorbing compound 1 100.0 parts by mass Isophorone diisocyanate 74.0 parts by mass When it was confirmed that the absorption of the isocyanate group had completely disappeared in the infrared absorption spectrum, the synthesis was terminated and the mixture was cooled to obtain oxygen-absorbing compound 2. Then, the oxygen-absorbing compound 2 was dissolved in ethyl acetate to prepare an oxygen-absorbing compound solution 2 having a solid content of 80 mass %.

[0129] [Oxygen absorbing compound 3] First, add the following ingredients to a flask equipped with a nitrogen inlet tube, a stirrer, and a condenser, and stir. The reaction was carried out at an internal temperature of 80 to 90°C for 8 hours. Oxygen absorbing compound 1 100.0 parts by mass Polyisocyanate solution 1 212.5 parts by weight When it was confirmed that the content of NCO groups in the solid content of the reaction liquid by the amine equivalent method reached approximately 0.64 mass %, the synthesis was terminated, the liquid was cooled, and the solvent was removed to obtain oxygen-absorbing compound 3. Then, the oxygen-absorbing compound 3 was dissolved in ethyl acetate to prepare an oxygen-absorbing compound solution 3 having a solid content of 60 mass %.

[0130] [Oxygen absorbing compound 4] First, the following raw materials were added to a flask equipped with a nitrogen inlet tube, a stirrer, and a condenser, and the mixture was reacted at an internal temperature of 80 to 90° C. for 8 hours with stirring. Oxygen absorbing compound 1 100.0 parts by mass Polyol solution 1 682.3 parts by mass Polyisocyanate solution 1 265.6 parts by mass When it was confirmed that the absorption of the isocyanate group had completely disappeared in the infrared absorption spectrum, the synthesis was terminated, and the mixture was cooled and the solvent was removed to obtain oxygen-absorbing compound 4. Then, the oxygen-absorbing compound 4 was dissolved in ethyl acetate to prepare an oxygen-absorbing compound solution 4 having a solid content of 60 mass %.

[0131] [Oxygen-absorbing compound 5] Oxygen absorbing compound 5 was obtained in the same manner as in the above-mentioned oxygen absorbing compound 4, except that polyol solution 2 was used instead of polyol solution 1. Then, the oxygen-absorbing compound 5 was dissolved in ethyl acetate to prepare an oxygen-absorbing compound solution 5 having a solid content of 60 mass %.

[0132] [Oxygen-absorbing compound 6] The following raw materials were charged into a flask equipped with a nitrogen inlet tube, a stirrer, and a condenser, and the reaction was carried out for 6 hours at an internal temperature of 80 to 90°C with stirring. Hydroxyl-terminated polyisoprene 1 100.0 parts by mass Isophorone diisocyanate 4.7 parts by weight When it was confirmed by infrared absorption spectroscopy that the absorption of the isocyanate group had completely disappeared, the synthesis was terminated and the mixture was cooled to obtain oxygen-absorbing compound 6, which was a urethane polyol. The number average molecular weight of the obtained oxygen absorbing compound 6 was 7,000. Then, the oxygen absorbing compound 6 was dissolved in ethyl acetate to prepare an oxygen absorbing compound solution 6 having a solid content of 60 mass %.

[0133] Table 2 shows the composition of the reaction solution used in synthesizing oxygen-absorbing compounds 2 to 6. Moreover, the charged compositions of oxygen-absorbing compound solutions 2 to 6 are summarized in Table 3.

[0134] [Table 2]

[0135] [Table 3]

[0136] <Preparation of oxygen-absorbing adhesive composition> (Preparation of oxygen-absorbing adhesive composition A1) The following raw materials were mixed at room temperature and homogenized to obtain an oxygen-absorbing adhesive composition A1, which was then subjected to various evaluations. Oxygen absorbing compound solution 2 100 parts by mass Polyol solution 1 100 parts by weight Polyisocyanate solution 1 10 parts by weight Oxidation promoting catalyst solution 1 1 part by mass Ethyl acetate 140 parts by weight

[0137] (Preparation of oxygen-absorbing adhesive compositions A2 to A9 and B1 to B2) According to the formulations in Tables 4 and 5, oxygen-absorbing adhesive compositions A2 to A9 and B1 to B2 were obtained in the same manner as for oxygen-absorbing adhesive composition A1.

[0138] [Table 4]

[0139] [Table 5]

[0140] [Table 6]

[0141] [Example 1] (Preparation and evaluation of oxygen absorbing laminates for molded parts) The oxygen absorbing adhesive composition A1 was applied to the PVC-PVDC composite film 1 as the substrate layer at a dry coating amount of 3 g / m 2 After applying and drying, the LLDPE film for the sealant layer is applied. The film was laminated with Film 1 and aged at 40° C. for 3 days to produce an oxygen-absorbing laminate for molded parts having the layer structure shown below, and various evaluations were carried out. Layer structure: PPVC-PVDC composite film 1 (240 μm) / oxygen absorbing adhesive composition A1 (3 g / m 2 ) / LLDPE film 1 (50 μm)

[0142] (Production and evaluation of oxygen-absorbing blister packaging containers) First, a thermal adhesive consisting mainly of vinyl chloride-vinyl acetate-maleic acid copolymer resin was applied to the matte surface of an aluminum foil having a thickness of 17 μm at a dry coating amount of 5.5 g / m 2 Gravure The coating was applied using Accoat, and the coating was dried at a surface actual temperature of about 150°C for a drying time of about 4 seconds to form a thermal adhesive layer, thereby producing a lid packaging material. Meanwhile, using a blister pack molding machine (manufactured by CKD Corporation), an oxygen-absorbing molded part having a recess and a fringe portion was produced from the oxygen-absorbing laminate for molded parts obtained above, so that the sealant layer was in contact with the contents at the recess. The sealant layers of the lid packaging material obtained above were then stacked facing each other, and the fringe portions were heat sealed to obtain oxygen-absorbing blister packaging containers, which were then subjected to various evaluations.

[0143] [Examples 2 to 9, Comparative Examples 1 to 3] In accordance with the descriptions in Tables 7 and 8, the oxygen-absorbing adhesive composition A1 in Example 1 was replaced with any of the oxygen-absorbing adhesive compositions A2 to A9, B1, B2, and DL adhesive 1, and the same procedures were carried out as in Example 1 to produce oxygen-absorbing laminates for molded parts, oxygen-absorbing molded parts, and oxygen-absorbing blisters. - A packaging container was obtained and evaluated in the same manner.

[0144] [Example 10] (Preparation and evaluation of oxygen absorbing laminates for molded parts) First, DL adhesive 1 was applied to the corona-treated surface of PET film 1 at a dry coating amount of 3 g / m 2 Nina After the coating was applied and dried as required, the aluminum foil 1 was attached by dry lamination. Then, oxygen-absorbing adhesive composition A1 was applied to the surface of the laminated aluminum foil so that the dry coating amount was 3 g / m2 and dried, after which it was laminated with LLDPE film 1 and cured at 40°C for 3 days to produce an oxygen-absorbing packaging material for molded parts, and various evaluations were carried out. Layer structure: PET film 1 (12 μm) / DL adhesive 1 (3 g / m 2 ) / Aluminum foil 1 (30 μm) / oxygen absorbing adhesive composition A1 (3 g / m 2 ) / LLDPE film 1( 50μm)

[0145] (Production and evaluation of oxygen-absorbing blister packaging containers) The same procedures as in Example 1 were carried out to obtain an oxygen-absorbing laminate for molded parts, an oxygen-absorbing molded part, and an oxygen-absorbing blister packaging container, and these were evaluated in the same manner.

[0146] [Comparative Example 4] Except for changing the oxygen-absorbing adhesive composition A1 to DL Adhesive 1, the same procedures as in Example 9 were performed to obtain an oxygen-absorbing laminate for molded parts, an oxygen-absorbing molded part, and an oxygen-absorbing blister packaging container, and these were evaluated in the same manner.

[0147] [Table 7]

[0148] [Table 8]

[0149] <Summary of results> The oxygen absorbing laminates for molded parts or the oxygen absorbing blister packaging containers of all the Examples exhibited a balance between excellent laminate strength, oxygen absorption amount, and low odor. On the other hand, the laminates and blister packaging containers of the comparative examples showed poor results in any of the lamination strength, oxygen absorption amount, and low odor property.

[0150] <Evaluation method>

[0151] [Oxygen absorption] The obtained lid part and the flange part of the tray-shaped molded part having a recess were heat-sealed together under nitrogen substitution. Then, 1400cc / m2 of solution was poured into the container using a syringe. 2 Air, Viscous The injected part was repaired with adhesive tape, and the product was stored in a thermostatic chamber at 25°C for 14 days. The air in the recess was then sampled with a syringe to measure the oxygen concentration, and the amount of oxygen absorbed was calculated. The oxygen concentration was measured using a zirconia-type oxygen concentration meter (manufactured by Toray Industries, Inc.).

[0152] [Laminate strength] A rectangular test piece 15 mm wide was prepared from the obtained oxygen-absorbing laminate, and the laminate strength between the layers via the oxygen-absorbing adhesive layer was measured using a tensile tester at a tensile speed of 50 mm / min.

[0153] [Odor sensory evaluation] After measuring the amount of oxygen absorbed, the inside of the blister packaging container was smelled and the odor was judged according to the following criteria: The odor originating from the sealant layer was excluded from the judgment. Evaluation criteria: 0: Odorless 1: Faint odor 2: Weak odor 3: Moderate odor 4: Strong odor [Explanation of symbols]

[0154] 1. Oxygen-absorbing laminate for molded parts, oxygen-absorbing packaging material for molded parts 2 Base material layer 3. Oxygen Barrier Layer 4. Oxygen-absorbing adhesive layer 5 Sealant Layer 7 General purpose adhesive layer 8 Reinforcement layer 10. Oxygen-absorbing blister packing container 11 Oxygen-absorbing molded parts 12 Contents storage recess 13 Flange 14 Lid parts

Claims

1. An oxygen-absorbing laminate for a molded part, which is used for a molded part of a blister packaging container, includes a layer structure in which at least a base layer, an oxygen barrier layer, an oxygen-absorbing adhesive layer, and a sealant layer are laminated in this order, The oxygen-absorbing adhesive layer is a layer formed from an oxygen-absorbing adhesive composition, The oxygen-absorbing adhesive composition contains at least an oxygen-absorbing compound and an oxidation-promoting catalyst, The oxygen absorbing compound has one or more unsaturated five-membered rings at the terminal of the main chain of the molecule, or at the terminals of the main chain and side chain of the molecule, any bond between the five carbon atoms constituting the unsaturated five-membered ring is a carbon-carbon double bond; A monovalent and / or divalent or higher electron-donating organic group 1 is bonded to the unsaturated five-membered ring, When the number of the unsaturated five-membered ring is one, the five-membered ring or the organic group 1 has a functional group having an active hydrogen or a group in which the active hydrogen of the functional group having an active hydrogen is substituted with a monovalent organic group 2, When the number of the unsaturated five-membered rings is two or more, the unsaturated five-membered rings are bonded to each other via a divalent or higher organic group 2 which substitutes an active hydrogen of an active hydrogen group on each of the five-membered rings or the organic group 1. Oxygen absorbing laminate for molded parts.

2. the structure of the unsaturated five-membered ring or the structure consisting of the unsaturated five-membered ring and organic group 1 is derived from one or more members selected from the group consisting of cyclopentadiene, dicyclopentadiene, norbornene, and derivatives thereof; 2. The oxygen absorbing laminate for molded parts according to claim 1.

3. The organic group 2 includes a structural portion derived from an isocyanate-based compound, or an isocyanate-based compound and a hydroxyl group-containing compound.

3. The oxygen-absorbing laminate for molded parts according to claim 1 or 2.

4. The isocyanate compound is xylene diisocyanate, hexamethylene diisocyanate, one or more selected from the group consisting of isocyanate, isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, and derivatives thereof; The oxygen absorbing laminate for molded parts according to claim 3.

5. the hydroxyl group-containing compound is one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof; 5. The oxygen-absorbing laminate for molded parts according to claim 3 or 4.

6. The organic group 2 does not have a crosslinkable functional group. The oxygen-absorbing laminate for molded parts according to any one of claims 1 to 5.

7. The organic group 2 has one or more crosslinkable functional groups, the crosslinkable functional group is a hydroxyl group and / or an isocyanate group; The oxygen-absorbing laminate for molded parts according to any one of claims 1 to 5.

8. The oxygen-absorbing compound contains one or more compounds selected from the group consisting of compounds represented by the following formulas (1) to (4): The oxygen-absorbing laminate for molded parts according to any one of claims 1 to 5. 【Chemistry 1】 【Chemistry 2】 【Chemistry 3】 【Chemistry 4】 (In the formula, a to e are each a number of 1 or more, and R 1 , R 2 , R 3 Each of the groups is an organic group having one or more carbon atoms, contains at least an alkylene and / or phenylene structure, and further contains a polyvalent It may contain a structure derived from one or more selected from the group consisting of alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof.

9. The oxygen-absorbing compound contains a compound represented by the following formula (5): The oxygen-absorbing laminate for molded parts according to any one of claims 1 to 5. 【Chemistry 5】 (In the formula, f is a number of 0 or more, and R 4 and R 5 Each of the above is an organic group having one or more carbon atoms, containing at least an alkylene and / or phenylene structure, and may further contain a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof.

10. The oxidation-promoting catalyst is a peroxide or a compound containing a cation of a transition metal. The oxygen absorbing laminate for molded parts according to any one of claims 1 to 9.

11. The compound containing a cation made of a transition metal is a metal soap made of a transition metal compound capable of releasing a cation or complex made of a transition metal and an anion or ligand made of a fatty acid. The oxygen-absorbing laminate for molded parts according to any one of claims 1 to 10.

12. The oxygen absorbing adhesive composition further contains a modifier, 12. The oxygen-absorbing laminate for molded parts according to claim 1, wherein the modifying agent contains an isocyanate compound and / or a hydroxyl group-containing compound.

13. The isocyanate compound is one or more selected from the group consisting of xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, and derivatives thereof.

13. The oxygen absorbing laminate for molded parts according to claim 12.

14. the hydroxyl group-containing compound comprises one or more selected from the group consisting of polyester polyols, poly(meth)acrylic acid ester polyols, polyalkylene ether diols, and urethane chain-extended polyols thereof; 14. The oxygen absorbing laminate for molded parts according to claim 12 or 13.

15. An oxygen-absorbing packaging material for molded parts of a blister packaging container, produced using the oxygen-absorbing laminate for molded parts according to any one of claims 1 to 14.

16. An oxygen-absorbing molded part for a blister packaging container, produced using the oxygen-absorbing packaging material for molded parts of a blister packaging container according to claim 15.

17. An oxygen-absorbing blister packaging container produced using the oxygen-absorbing molded part of the blister packaging container according to claim 16, The oxygen barrier layer is a layer located outside the oxygen absorbing adhesive layer. Oxygen absorbing blister packaging container.